Photoelectric conversion thin film element and method for manufacturing the same
Patent Information
- Application Number
- JP2024185036
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-09
AI Technical Summary
【0028】 本発明の光電変換素子(または太陽電池)は、ペロブスカイト型構造を有する化合物を 含むペロブスカイト層と、ポリシランを含むポリシラン層と、これらの層の間に介在し、 p型半導体を含む電子ブロック層とを有するため、大気中で高温熱処理によりペロブスカ イト層を形成しても、長期間に亘って、変換効率を大きく低下することなく維持または向 上できる(高い耐久性を示す)。また、前記光電変換素子は高い変換効率を示すこともで きる。さらに、本発明の方法では、高い耐久性を示すペロブスカイト型の光電変換素子を 簡便にまたは効率よく(高い生産性で)製造できる。
Smart Images

Figure 2025003548000009 
Figure 2025003548000010 
Figure 2025003548000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a photovoltaic device having a perovskite layer including a compound having a perovskite structure. The present invention relates to a conversion thin-film element (or a photoelectric conversion element) and a manufacturing method thereof. [Background technology]
[0002] As a renewable energy source to replace fossil fuels and nuclear power, we are using inexhaustible, clean solar power. Solar power generation, which can be used to improve the energy efficiency of homes, has been attracting a lot of attention. However, the high price is a major problem. This is the biggest obstacle to the widespread use of solar cells, and in order to further popularize them, it is necessary to reduce costs and Efficiency is essential.
[0003] Perovskite solar cells using compounds with perovskite structures as light absorption layers It can be molded by simple methods such as coating without the need for a vacuum process, and the raw materials are Because they are relatively inexpensive, manufacturing costs can be significantly reduced compared to conventional solar cells. In particular, the development of low-cost, lightweight solar cells with high power generation efficiency is being pursued. It is possible to use this technology and it is also compatible with indoor light wavelengths, so it has been attracting worldwide attention for several years. For example, various perovskite solar cells are prepared in Patent Documents 1 to 3.
[0004] On the other hand, Patent Documents 4 and 5 disclose photoelectric conversion devices that contain polysilane in the perovskite layer or hole transport layer. A substitution element is described. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-13982 A [Patent Document 2] JP 2019-38714 A [Patent Document 3] JP 2019-12819 A [Patent Document 4] JP 2018-98276 A [Patent Document 5] JP 2019-68018 A Summary of the Invention [Problem to be solved by the invention]
[0006] In perovskite solar cells, the methyl group in the perovskite crystal (perovskite structure) Ammonium (CH3NH3 + ) There is concern that the device characteristics may become unstable due to ion desorption, etc. Due to this crystal instability, If the heat treatment temperature is too high in the process of extending the life of the battery, the conversion efficiency will decrease rapidly. Perovskite crystals (perovskite layers) have traditionally been grown in an inert gas atmosphere at 100°C. It is produced at a low heat treatment temperature.
[0007] In the examples of any of Patent Documents 1 to 3, the light absorption layer (perovskite layer) The hole transport layer is heat-treated at about 65 to 100°C in a glove box filled with nitrogen gas. Not only is it not possible to improve productivity sufficiently, but durability is also not specifically There is nothing stated in.
[0008] In the examples of Patent Document 4, the perovskite layer and the hole transport layer are also heated to 100° C. However, there is no description about the gas atmosphere. It is said that it shows high photoelectric conversion efficiency (conversion efficiency or power generation efficiency), but durability is not yet known. There is no specific mention of gender.
[0009] In the examples of Patent Document 5, the perovskite layer is heat-treated at 100° C. in an air atmosphere. It was reported that the addition of polysilane to the perovskite layer led to the formation of PbI2. However, there is no specific description of the improvement in durability. It has not been done.
[0010] Therefore, the object of the present invention is to provide a method for forming a perovskite layer by high-temperature heat treatment in the atmosphere. Perovskite-type solar cells that can maintain or improve conversion efficiency over a long period of time (high durability) The present invention provides a photoelectric conversion element and a method for manufacturing the same. [Means for solving the problem]
[0011] As a result of intensive research to achieve the above object, the present inventors have discovered a method for manufacturing a perovskite layer and a poly A silane layer and an electron block interposed between the perovskite layer and the polysilane layer. In the case of a photoelectric conversion element including the above-mentioned layer, even if it is produced by performing a high-temperature heat treatment in the atmosphere, it does not last for a long period of time. The present invention has been accomplished by finding that the conversion efficiency can be maintained or improved.
[0012] That is, the photoelectric conversion element of the present invention is a perovskite-type photoelectric conversion element that includes a compound having a perovskite structure. a perovskite layer, a polysilane layer containing polysilane, and a perovskite layer and a polysilane layer containing polysilane. and an electron blocking layer interposed between the polysilane layers and including a p-type semiconductor.
[0013] The polysilane is selected from structural units represented by the following formulas (2a) and (2b): It may contain at least one type of structural unit.
[0014] [ka]
[0015] (In the formula, R 1 ~R 3 are each independently a hydrogen atom, a hydroxyl group, an organic group, or a silicon (representing the aryl group).
[0016] In the formula (2a), R 1 and R 2 At least one of the above is an aryl group-containing group. In the formula (2b), R 3 may be an aryl group-containing group. The ratio of the structural unit represented by a) is about 50 mol % or more with respect to the entire polysilane. The polysilane may be a cyclic polysilane. may be about 50 to 100% by mass with respect to the entire polysilane layer.
[0017] The compound having a perovskite structure is a compound represented by the following formula (1): Good too.
[0018] AMX3(1) wherein A is selected from organic ammonium, amidinium and alkali metal ions. M represents a monovalent cation including at least one of the elements of Group 14 of the Periodic Table and the elements of Group 2 of the Periodic Table. represents a divalent cation of at least one metallic element selected from the group consisting of halogen (Indicates the chloride ion.)
[0019] The compound having a perovskite structure is represented by the formula (1), where A is methyl Ammonium and C 2-4 Alkylammonium, C 1-4 Amidinium, sodium i At least one selected from the group consisting of ions, potassium ions, rubidium ions and cesium ions. and a second monovalent cation. The ratio of the total amount of the second monovalent cation to the former / latter (molar ratio) is 40 / 60 to 98 / 2. It may be to some extent.
[0020] The compound having a perovskite structure is represented by the formula (1), and at least one second halide ion selected from bromide ions and chloride ions. The iodide ion and the second halide ion may be included. The ratio of the total amount of the product ions to the former / latter (molar ratio) is about 80 / 20 to 98 / 2. Good too.
[0021] The p-type semiconductor contained in the electron blocking layer is a compound represented by the following formula (1b): It's fine.
[0022] MX2(1b) (wherein M and X are the same as in formula (1) above).
[0023] The photoelectric conversion element may further include a hole transport layer.
[0024] The present invention relates to a perovskite compound for forming the compound having a perovskite structure. A polysilane layer containing polysilane is laminated on one side of the film containing the precursor to form a pre-laminate. and heat-treating the preliminary laminate obtained in the polysilane layer forming step. and a heat treatment to form a laminate including a perovskite layer, an electron blocking layer, and a polysilane layer. The manufacturing method of the photoelectric conversion element includes the steps of: A hole transport layer forming step is then performed in which a hole transport layer is laminated on the polysilane layer of the laminate obtained in the treatment step. The heat treatment temperature in the heat treatment step is about 150 to 250° C. The polysilane layer forming step and the heat treatment step may be performed in the atmosphere, Furthermore, the hole transport layer forming step may also be carried out in the air.
[0025] In addition, the present invention may solve the following problems as a secondary object. Another object of the present invention is to provide a perovskite-type photoelectric conversion element exhibiting high conversion efficiency and a method for producing the same. The purpose of the Act is to provide a law.
[0026] Still another object of the present invention is to provide a method for producing a perovskite-type photoelectric conversion element having high durability in a simple and easy manner. Another object of the present invention is to provide a method for producing the same quickly and efficiently (with high productivity).
[0027] In the present specification and claims, the number of carbon atoms of a substituent is defined as C1, C6, C 10 For example, "C1 alkyl group" refers to an alkyl group with one carbon atom. It means "C 6-10 The term "aryl group" refers to an aryl group having 6 to 10 carbon atoms. Effect of the Invention
[0028] The photoelectric conversion element (or solar cell) of the present invention comprises a compound having a perovskite structure. a perovskite layer including a polysilane and a polysilane layer including a polysilane, Since it has an electron blocking layer containing a p-type semiconductor, perovskite can be formed by high-temperature heat treatment in air. Even if a thin film is formed, the conversion efficiency is maintained or improved without a significant decrease over a long period of time. In addition, the photoelectric conversion element can exhibit high conversion efficiency. Furthermore, the method of the present invention can produce a perovskite-type photoelectric conversion element that exhibits high durability. It can be produced easily and efficiently (with high productivity). [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a schematic diagram of a photoelectric conversion element prepared in an example. [Diagram 2] FIG. 2 shows X-ray diffraction patterns of the photoelectric conversion elements produced in Example 7 and Comparative Example 4 at an early stage after production. [Diagram 3] FIG. 3 is a graph showing the change over time in photoelectric conversion efficiency of the photoelectric conversion elements produced in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] [Configuration of photoelectric conversion element] The photoelectric conversion element of the present invention (perovskite-type photoelectric conversion element) has a perovskite structure. A perovskite layer including a compound having the formula (also simply referred to as a perovskite compound) and a poly and a polysilane layer containing silane. It is preferable that the semiconductor device further includes an electron blocking layer that is interposed between the polysilane layers and contains a p-type semiconductor. It is.
[0031] The photoelectric conversion element includes, for example, a first electrode (transparent electrode), an electron transport layer (ETL), a hole (or hole) transport layer (HTL), a second electrode (metal or carbon electrode), etc. A typical structure may be, for example, a first electrode / electron transport layer (ETL) / Perovskite layer / electron blocking layer / polysilane layer / hole transport layer / second electrode in that order. Stacked planar heterojunction type [or Planar type (normal structure)]; the planar heterojunction The reverse structure type [or Plana r(OPV) type (inverted structure)]; electron transport in the perovskite layer in the planar heterojunction type A porous portion including a porous oxide is formed adjacent to the electron transport layer in the vicinity of the interface with the electron transport layer. A layer ( Nanostructure type (or Meso-porous type) containing the first perovskite layer (described later) The structure of the photoelectric conversion element may be any structure. In order to improve the characteristics such as conversion efficiency and to increase the surface area, nano-structured That is, as shown in FIG. 1, a first electrode 1 / electron transport layer 2 / porous portion and a perovskite First perovskite layer 3a containing a perovskite compound / second perovskite layer 3b containing a perovskite compound The structure includes a scite layer 3b, an electron blocking layer 4, a polysilane layer 5, a hole transport layer 6, and a second electrode 7. It is preferable that the above-mentioned layers are laminated in this order.
[0032] (Perovskite layer) The perovskite layer (first perovskite layer 3a and / or second perovskite layer The layer 3b) may contain at least a perovskite compound. The material is preferably a compound having a perovskite structure represented by the following formula (1).
[0033] AMX3(1) [wherein A (or the A site) is an organic ammonium, amidinium, or alkali metal iridium] represents a monovalent cation containing at least one selected from the group consisting of ions, (M site or B site) is selected from the group 14 elements of the periodic table and the group 2 elements of the periodic table. represents a divalent cation (divalent metal ion) of at least one metallic element, and X (or X site) represents a halide ion (halogen anion).
[0034] In the formula (1), examples of the organic ammonium represented by A include methyl ammonium. ammonium (also known as CH3NH3 or MA), ethylammonium (CH3CH2NH 3 or EA), n-propylammonium, isopropylammonium, n- Butylammonium, isobutylammonium, s-butylammonium, t-butylammonium Alkyl ammonium such as C 1-6 Alkyl ammonium; C such as Nilinium 6-10 Aryl ammonium; benzyl ammonium, phenethyl Ammonium and other C 6-10 Aryl C 1-6 Alkyl ammonium etc. These organic ammonium salts may be used alone or in combination of two or more. .
[0035] Examples of the amidinium represented by A include formamidinium [HC(NH2)2 or FA], acetamidinium, propionamidinium, etc. 1-6 a These amidiniums can be used alone or in combination of two or more. It may also be included.
[0036] Examples of the alkali metal ion represented by A include a lithium ion and a sodium ion. These include potassium ions, rubidium ions, and cesium ions. The potassium metal ions may be contained alone or in combination of two or more kinds.
[0037] Perovskite compounds contain one or more of these monovalent cations represented by A. The above may be included in combination, and may be selected from organic ammonium and amidinium. It is preferable that the organic-inorganic perovskite compound contains at least one organic ammonia. It is more preferable that the initial (element) contains at least an alkyl ammonium. Conversion efficiency (short-circuit current density and / or open-circuit voltage) after a long period of time It is particularly preferable that the composition contains at least methylammonium from the viewpoint of facilitating improvement of the properties. Although ethylammonium is an unstable ion that is easily desorbed, when the ionic radius is taken into consideration, , tolerance factor compared to alkali metals (empirical index for estimating the stability of the perovskite structure) ) is easily brought close to 1 and the cubic crystal structure is easily stabilized. Therefore, if the desorption can be effectively suppressed, The inclusion of methylammonium is preferred in that a stable crystal structure can be formed.
[0038] The ratio of methylammonium in A (A site) to the total A is, for example, 10 molar. % or more, and the preferred ranges are as follows: 30 to 100 mol %, 40 to 98 mol %, mol%, 45 to 90 mol%, 50 to 80 mol%. A is an amidinium compound such as formamidinium. When it contains alkali metal ions such as midium and / or potassium ions, methyl The proportion of ammonium is, for example, 55 to 75 mol % relative to the total amount of A, and preferably 6 A is an alkyl group having 2 or more carbon atoms, such as ethylammonium, which will be described later. When ammonium is included, the ratio of methylammonium to the total A is, for example, 70 to 100%. 98 mol %, preferably 80 to 96 mol %, and more preferably 85 to 95 mol %. If the ratio of methylammonium is too low, the conversion efficiency (short circuit current) at the initial stage or after a long period of time decreases. current density and / or open circuit voltage) may decrease, or it may become difficult to stabilize the crystal structure. On the other hand, if it is too high, durability cannot be sufficiently improved, and the initial conversion efficiency (short circuit current density) may decrease. It may become difficult to improve the resistance (temperature and / or open circuit voltage).
[0039] Perovskite compounds containing methylammonium as A are It is known that the crystal structure is unstable and durability is low because the molecules are easily separated. In the device, a polysilane layer is stacked on a perovskite layer via an electron blocking layer. Therefore, even if the A site contains methylammonium, the desorption can be effectively suppressed, and durability is improved. It seems that it can be improved.
[0040] Also, if A contains methylammonium (also called the first monovalent cation), then A is Methylammonium alone may be used, but other monovalent cations different from methylammonium may also be used. A may be included in combination with On. A stabilizes the perovskite crystal structure and provides durability. From the viewpoint of improving the properties, alkyl ammonium and amidinium having two or more carbon atoms are permitted. Large cations that can improve the tolerance factor; and At least one monovalent cation selected from alkali metal ions that do not separate (second one It is preferred that the cations contain cations of 1 to 4 carbon atoms.
[0041] Examples of alkyl ammonium having 2 or more carbon atoms include organic ammonium. C such as alkyl ammonium (excluding methyl ammonium) 2-6 Alki ammonium, preferably C2-4 Alkyl ammonium, more preferably Or C 2-3 Alkyl ammonium is preferred, with ethyl ammonium being particularly preferred.
[0042] Examples of the amidinium include the same as those exemplified above, and preferably C 1-4 Amiji nium, more preferably C 1-3 amidinium, more preferably C 1-2 Amidinium and formamidinium is particularly preferred.
[0043] Examples of alkali metal ions that do not desorb at room temperature, for example, at about 25° C., include sodium ions. Examples of the ions include Cr ions, potassium ions, rubidium ions, and cesium ions. Mostly potassium ions.
[0044] A contains these second monovalent cations alone or in combination of two or more kinds. Of these second monovalent cations, C 2-4 Alkylammonium, C 1- 4. Amidinium, sodium ion, potassium ion, rubidium ion and cesium It is preferable that the ion contains at least one selected from the group consisting of C 2-3 Alkyl ammonium M, C 1-3 A few ions selected from amidinium, sodium ions and potassium ions More preferably, the compound contains at least one of ethylammonium, formamidinium and kalium. It is more preferable that the cation contains at least one selected from the group consisting of ethyl ion and ethyl ion. Preferably, the ion exchange agent contains ammonium ions or formamidinium and potassium ions. Preferably, it contains formamidinium and potassium ions, particularly preferably.
[0045] The ratio of methylammonium (the first monovalent cation) to the total amount of the second monovalent cation In this case, for example, the molar ratio of the former to the latter is selected from the range of about 10 / 90 to 100 / 0. The preferred ranges are as follows: 30 / 70~100 / 0, 40 / 60~ 98 / 2, 45 / 55~90 / 10, 50 / 50~80 / 20. A is Holm Amiji containing amidinium ions such as nium and / or alkali metal ions such as potassium ions In this case, the ratio is, for example, the former / latter (molar ratio)=55 / 45 to 75 / 25, The ratio is preferably 60 / 40 to 70 / 30. A is an ammonium salt having 2 or more carbon atoms, such as ethylammonium. In the case where the alkyl ammonium compound is an alkyl ammonium compound, the ratio is, for example, the former / the latter (molar ratio)=70. / 30 to 98 / 2, preferably 80 / 20 to 96 / 4, more preferably 85 / 15 to 9 If the ratio of methylammonium is too low, the initial or long-term changes The conversion efficiency (short circuit current density and / or open circuit voltage) decreases, and the crystal structure becomes difficult to stabilize. If the ratio of the second monovalent cation is too low, durability may not be improved sufficiently. In addition, carbon black such as ethylammonium may be used as the second monovalent cation. If the proportion of alkylammonium with a prime number of 2 or more is too high, the tolerance factor will exceed 1 and the crystal structure will may become unstable.
[0046] In addition, the second monovalent cation is an amidinium such as formamidinium, and potassium. When an alkali metal ion such as tungsten ion is combined with the tungsten ion, the ratio of the two is, for example, The molar ratio of the first to the second may be selected from the range of about 1 / 99 to 99.9 / 0.1, and is preferably The new ranges are as follows: 50 / 50~99.5 / 0.5, 60 / 40~99 / 1, 70 / 30 to 98 / 2, 75 / 25 to 95 / 5, and more preferably 80 / 20 The ratio is 90 / 10. The ratio is the ratio of formamidinium ions to potassium ions. If the proportion of amidinium such as formamidinium is too low, the tolerance factor The ions in the alkali metals, such as potassium ions, may become smaller and the crystal structure may become unstable. If the proportion of group ions is too low, there is a risk that unstable ions such as MA may be easily desorbed. do.
[0047] In the formula (1), examples of elements corresponding to the divalent metal ion represented by M include For example, elements in Group 14 of the Periodic Table, such as lead (Pb), tin (Sn), and germanium (Ge); Ra, Barium (Ba), Strontium (Sr), Calcium (Ca), Magnesium (Mg) Examples include elements in Group 2 of the periodic table (or alkaline earth metals) such as magnesium (Mg). M may contain these divalent metal ions alone or in combination of two or more. Among these elements corresponding to M, Pb, Sn, and Ge are group 14 elements in the periodic table. As the group 2 elements of the periodic table, Ba, Sr, Ca, and Mg are preferable, and among them, P Elements in Group 14 of the periodic table, such as b and Sn, are preferred, with Pb being particularly preferred.
[0048] The ratio of Pb ions in M (M site) is, for example, about 10 mol% with respect to the entire M. The preferred ranges are as follows, in stages: 30 mol % or more, 50 mol % or more, 70 mol % or more, It is preferably at least 90 mol %, more preferably at least 90 mol %, and even more preferably substantially 100 mol %.
[0049] In the above formula (1), the halide ion (halogen anion) represented by X Examples of halogen elements that can be used include iodine (I), bromine (Br), and chlorine (Cl). X may include any one of these halide ions alone or in combination of two or more. Of these halide ions, iodide ion (I - ) is preferred stomach.
[0050] The ratio of iodide ions in X (X site) is, for example, 10 mol% with respect to the total amount of X. The preferred ranges are as follows: 30 mol % or more, 50 mol % or more, 7 0 mol % or more, 90 mol % or more, more preferably 95 mol % or more, substantially 10 If the proportion of iodide ions is too low, the perovskite crystals may not form. There is a risk that crystals may not form.
[0051] In addition, when X contains an iodide ion (also called a first halide ion), the iodide The compound is composed of a halide ion (also called a second halide ion) different from the halide ion. When combined, the initial conversion efficiency (short circuit current density and / or open circuit voltage) and durability In some cases, this can improve the durability of the material. On (Br - ), chloride ion (Cl - ) and the like. X is a second halide The second halogen ions may be used alone or in combination of two or more. The chloride ion is a bromide ion.
[0052] The total amount of iodide ions (first halide ions) and second halide ions The ratio of the former / latter (molar ratio) is selected from the range of about 10 / 90 to 100 / 0. The preferred ranges are as follows: 30 / 70 to 100 / 0, 50 / 5 0~100 / 0, 70 / 30~99 / 1, 80 / 20~98 / 2, 90 / 10~97 / 3 The ratio of iodide ions is preferably 95 / 5 to 97 / 3. If the ratio of the second halide ion is too high, the perovskite crystal may not be formed. If the amount is too small, the initial conversion efficiency (short circuit current density and / or open circuit voltage) and durability will be insufficient. There is a risk that the improvement will not be achieved.
[0053] Representative perovskite compounds represented by the above formula (1) include those in which A is methylammonium. Ammonium (MA), ethylammonium (EA), formamidinium (FA) and potassium M contains at least one selected from lead (Pb) ions, and X contains at least one selected from lead (K) ions, At least one halides selected from iodine (I), bromine (Br), and chlorine (Cl) Compounds containing anions of halogen elements, such as MAPbI3, MAPbB r3, MAPbCl3, MAPbI 3-x1 Br x1 , MAPbI 3-x2 Cl x2 , M APbBr 3-x2 Cl x2 Compounds in which A is methylammonium (MA) ;MA 1-a1 EA a1 PbI3, MA 1-a1 EA a1 PbI 3-x1 Br x1 etc. Compounds in which A is formed with methylammonium (MA) and ethylammonium (EA) ;MA 1-a2 FA a2PbI3, MA 1-a2 FA a2 PbI 3-x1 Br x1 etc. Compounds where A is formed with methylammonium (MA) and formamidinium (FA) ;MA 1-a2-a3 FA a2 K a3 PbI3, MA 1-a2-a3 FA a2 K a3 Pb I 3-x1 Br x1 In these cases, A is methylammonium (MA), formamidinium (FA), etc. ) and potassium (K) ions. 1, a2, a3, x1, and x2 are each independently greater than 0 and less than 1.
[0054] These perovskite compounds may be used alone or in combination of two or more. Among the perovskite compounds, A contains at least methylammonium (MA) and M A compound in which X contains at least a lead (Pb) ion and X contains at least an iodine (I) anion. Among them, A is preferably methylammonium (MA) from the viewpoint of particularly excellent durability. ), ethylammonium (EA), formamidinium (FA) and potassium (K) and at least one selected from the group consisting of methylammonium (M A) and ethylammonium (EA), or A is methylammonium Compounds formed with ammonium (MA), formamidinium (FA) and potassium (K) A is preferably methylammonium (MA), formamidinium (F A) and potassium (K) are more preferred, and MA 1-a2-a3 F A a2 Ka3 PbI3 is particularly preferred.
[0055] In addition, A is the number of carbon atoms such as methylammonium (MA) and ethylammonium (EA). By using a perovskite compound formed with two or more alkyl ammoniums, It is easy to improve the short circuit current density; A is methylammonium (MA) and formamidinium ( It is formed by amidinium ions such as FA and alkali metal ions such as potassium (K). The use of a perovskite compound appears to facilitate improvement of the open circuit voltage of the device.
[0056] The ratio of the perovskite compound represented by the formula (1) in the perovskite layer is It may be selected, for example, from a range of about 10 mass % or more based on the entire perovskite compound. The preferred ranges are 30 to 100% by mass, 50 to 100% by mass, 70 to 100 mass%, 90 to 100 mass%, 95 to 100 mass%, and substantially 100 It is more preferable that it is expressed in mass %.
[0057] In the photoelectric conversion element of the present invention, the desorption of unstable ions such as MA is effectively suppressed. Even if the composition is the same as that of conventional perovskite crystals, the lattice constant a is slightly enlarged. For example, if the perovskite compound is MAPbI3, the conventional MAPbI3 The lattice constant a of the photoelectric conversion element of the present invention is about 6.276 to 6.282 Å. The lattice constant a of the perovskite compound is, for example, 6.286 to 6.292 Å, preferably 6.288 to 6.290 Å. Therefore, the perovskite structure of the photoelectric conversion element of the present invention The lattice constant a of the compound is 100°C, which is the same as that of the conventional perovskite compound (prepared by heat treatment at about 100°C). For example, the lattice constant a of the perovskite compound of the same composition is 0.003 to 0.0 15 Å, preferably 0.005 to 0.01 Å larger.
[0058] In this specification and claims, the lattice constant a is as described in the examples below. It can be measured by the method described below.
[0059] When the photoelectric conversion element is of the nanostructure type, the perovskite layer is adjacent to the electron transport layer. The porous portion includes a porous oxide, and the perovskite infiltrates (or impregnates) the porous portion. A first perovskite layer formed of a kite compound and a layer stacked on the first perovskite layer. and a second perovskite layer formed of a perovskite compound. It's okay to do that.
[0060] In the first perovskite layer, the porous oxide constituting the porous portion is typically For example, titanium oxide (IV), zinc oxide (II), tin oxide (IV), aluminum oxide Examples of metal oxides include tungsten (IV) oxide, zirconium (IV) oxide, etc. These metal oxides may be contained alone or in combination of two or more. Titanium(IV) oxide, zinc(II) oxide, tin(IV) oxide, etc. Metal oxides (participating in the transport) are preferred, with titanium(IV) oxide being particularly preferred. The compound may be different from the electron transport material forming the electron transport layer described later, but is usually the same. It is often one.
[0061] The average thickness of the first perovskite layer is selected from the range of, for example, about 100 to 1000 nm. The preferred ranges are as follows: 150 to 980 nm, 200 to 950 nm, The average thickness of the first perovskite layer (or the porous portion) is 300 to 900 nm. If it is too large, the manufacturing efficiency may decrease, and if it is too small, the conversion efficiency may decrease. There it is.
[0062] In the present specification and claims, the perovskite layer, the polysilane layer, The average thickness of each layer, such as the hole transport layer, was measured using a transmission electron microscope (TEM) or an atomic force microscope (AFM). It may also be measured by a method such as FM.
[0063] The second perovskite layer does not include a porous portion and includes a perovskite compound. The type of perovskite compound used in the second perovskite layer is the same as that of the first perovskite layer. The type of perovskite compound used in the perovskite layer may be the same or different. Well, usually they are the same.
[0064] The average thickness of the second perovskite layer (when the photoelectric conversion element is a planar heterojunction type or an inverted structure type) In this case, the average thickness of the perovskite layer is selected from the range of, for example, about 5 to 1000 nm. For example, the thickness can be selected from 10 to 500 nm, preferably from 30 to 300 nm, and more preferably from 50 to 500 nm. If the average thickness of the second perovskite layer is too large, the manufacturing efficiency and and conversion efficiency may decrease.
[0065] (Polysilane layer) The polysilane layer is a layer containing at least polysilane having excellent hole transport ability and heat resistance. In the photoelectric conversion element of the present invention, a polysilane layer is formed on the perovskite layer to form an electron blocking layer. Since the perovskite layer is layered through a crystalline layer, the perovskite layer is protected from unstable ions such as methylammonium. Even if the material contains unstable (or easily desorbed) ions, the durability can be significantly improved, and the initial conversion efficiency can be improved. The rate can be maintained or increased over a long period of time without significant degradation.
[0066] The reason for this is unclear, but it is thought that polysilane acts as an electron blocking layer on the perovskite layer. This is believed to be due to the fact that a dense interface structure (polysilane layer) can be formed by the The dense polysilane layer can effectively suppress the desorption of unstable ions such as methylammonium. While it acts as a protective film (protective layer) that can be used for the hole, the polysilane This is presumably due to the relatively high hole transport capacity, which allows for efficient transport. In the heat treatment process (crystal growth process) described later, the polysilane is grown at a high temperature. When heat-treated at temperatures around 1000 K, polysilane melts or becomes highly reactive, forming a denser polysilane. It is believed that a polysilane layer having a large surface area is formed.
[0067] On the other hand, the photoelectric conversion elements described in Patent Documents 4 and 5 are unstable even though they contain polysilane. The desorption of ions cannot be effectively suppressed, and it is difficult to sufficiently maintain or improve the conversion efficiency over a long period of time. In particular, Patent Document 5 describes how adding polysilane to a perovskite layer It is described that the generation of PbI2, which causes deterioration of the element, can be prevented, and deterioration of the element can be suppressed. However, it is effective in suppressing the desorption of methylammonium and other species from the surface of the perovskite layer. Cannot be controlled.
[0068] Polysilanes can be linear, cyclic, branched, and / or network-type polysilanes with Si-Si bonds. It is a compound having a shape (or a network shape) and is represented by the following formulas (2a) and (2b): It is preferable that the polymer has at least one of the structural units.
[0069] [ka]
[0070] (In the formula, R 1 ~R 3 are each independently a hydrogen atom, a hydroxyl group, an organic group, or a silicon (representing the aryl group).
[0071] In the above formulae (2a) and (2b), the group (or side chain) R 1 ~R 3 Organic Examples of the group include an alkyl group, an alkenyl group, a cycloalkyl group, and a cycloalkenyl group. Hydrocarbon groups such as alkyl groups, aryl groups, and aralkyl groups; ether groups corresponding to these hydrocarbon groups; groups such as alkoxy groups, cycloalkyloxy groups, aryloxy groups, aralkyl The organic group is usually an alkyl group, an alkenyl group, a cycloalkyl group, an oxy group, etc. In many cases, the alkyl group is a hydrocarbon group such as an alkyl group, an aryl group, or an aralkyl group. In many cases, the alkyl group is substituted at the end with a hydroxyl group, an alkoxy group, a silyl group, or the like.
[0072] R in the formulas (2a) and (2b) 1 ~R 3 In the above, the alkyl group is a methyl group. , ethyl group, propyl group, isopropyl group, n-butyl group, i-butyl group, s-butyl group , t-butyl group, pentyl group, hexyl group, etc. 1-14 Alkyl groups and the like. Preferably C 1-10 Alkyl groups, more preferably C 1-6 It is an alkyl group.
[0073] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, n-butoxy group, i-butoxy group, s-butoxy group, t-butoxy group, pentyloxy group C etc. 1-14 Examples of the alkyl group include an alkoxy group.
[0074] Alkenyl groups include vinyl, allyl, butenyl, and pentenyl groups. 2- 14 Alkenyl groups and the like.
[0075] Examples of the cycloalkyl group include a cyclopentyl group, a cyclohexyl group, and a methylcyclohexyl group. C such as silyl group 5-14 cycloalkyl groups, etc.
[0076] Examples of the cycloalkyloxy group include a cyclopentyloxy group and a cyclohexyloxy group. C etc. 5-14 Examples thereof include a cycloalkyloxy group.
[0077] Examples of the cycloalkenyl group include cyclopentenyl and cyclohexenyl groups. 5- 14 Examples thereof include cycloalkenyl groups.
[0078] The aryl group is a phenyl group, a methylphenyl group (a tolyl group), a dimethylphenyl group, C groups such as xylyl and naphthyl groups 6-20 Aryl groups and the like are included, and preferably C 6-15 Aryl groups, more preferably C 6-12 Aryl groups, more preferably phenyl groups. C such as aryl radicals 6-10 It is an aryl group.
[0079] Aryloxy groups include C aryloxy groups such as phenoxy and naphthyloxy groups. 6-20 Ally Examples of such groups include an aryloxy group.
[0080] Aralkyl groups include benzyl, phenethyl, and phenylpropyl groups. 6- 20 Aryl-C 1-6 Alkyl groups and the like.
[0081] Examples of the aralkyloxy group include a benzyloxy group, a phenethyloxy group, and a phenylpropoxy group. C such as pyroxy group 6-20 Aryl-C 1-6 Alkyloxy groups and the like.
[0082] The silyl group includes Si such as silyl, disilanyl, and trisilanyl groups. 1-10 Shira and the like, and preferably Si 1-6 It is a silanyl group.
[0083] Also, R 1 ~R 3 is an organic group such as an alkyl group or an aryl group, or a silyl group. has at least one hydrogen atom replaced by a substituent (or functional group). Such substituents (or functional groups) may be, for example, hydroxyl groups, alkyl groups, The groups may be the same as those exemplified above, such as an aryl group and an alkoxy group.
[0084] In addition, in formula (2a), R 1 and R 2 The types may be different from each other or may be the same. It is preferable that it is one.
[0085] These R 1 ~R 3 Among these, alkyl groups, such as methyl groups, 1-4 Alkyl group or aryl-containing groups such as aryl groups, e.g., C such as phenyl groups; 6-20 Aryl From the viewpoint of easily improving the hole transport efficiency after charge separation, it is preferable to use a group such as a . More preferably, the aryl group-containing group is at least one of the aryl groups represented by the formula (2a). is R 1 and R 2 At least one of R is preferably an aryl group-containing group. 1 and R 2 It is more preferable that both of the above formula (2b) are aryl group-containing groups. ) in R 3 is preferably an aryl group-containing group.
[0086] Examples of the aryl group-containing group include the aryl and aralkyl groups exemplified above as the organic group. The preferred aryl groups include the same as the aryl group, the aryloxy group, and the aralkyloxy group. Examples of the alkyl-containing group include phenyl, naphthyl, and biphenylyl groups. 6-12 Ally group, C 6-12 Aryl-C 1-6 Alkyl group, C 6-12 Aryloxy group, C 6- 12 Aryl-C 1-6 An alkoxy group is preferable, and a C 6-10 Aryl group, C 6-10 Aryl-C 1-4 Alkyl group, C 6-10 Aryloxy group, C 6-1 0Aryl-C 1-4 Among these aryl-containing groups, C 6-1 Aryl groups such as aryl groups are preferred, with phenyl groups being particularly preferred.
[0087] Preferred structural units include those represented by the formula (2a): 1 and R 2 One of the A structural unit in which the other is an alkyl group; R 1 and R 2 Both of the groups are aryl. A structural unit which is a group-containing group; in the formula (2b), R 3 is an aryl group-containing group Units include:
[0088] In the formula (2a), R 1 and R 2 Of these, one is an aryl group-containing group and the other is an aryl Examples of structural units that are alkyl groups include alkyl-aryl-silane units. Specifically, C 1-6 Alkyl-C 6-10 Aryl-silane units and the like.
[0089] In the formula (2a), R 1 and R 2 and a structural unit in which both of the above are aryl group-containing groups. Examples of such units include diaryl-silane units, specifically diphenyl-silane units. Run unit etc. 6-10 Aryl-silane units and the like.
[0090] In the formula (2b), R 3 Examples of the structural unit in which is an aryl group-containing group include aryl-silane units, specifically, C such as phenyl-silane units. 6- 10 Aryl-silane units and the like.
[0091] These structural units may be used alone or in combination of two or more. Among them, in formula (2a), R 1 and R 2 and Positions are preferred, with diphenyl-silane units being especially preferred.
[0092] The proportion of aryl-containing groups in the side chains of the polysilane is determined based on the total proportion of the side chains of the polysilane (e.g. , R 1 ~R 3 For example, the amount of the aryl group may be selected from a range of about 10 mol % or more relative to the total amount of the aryl group, The preferred ranges are as follows: 30 mol % or more, 50 mol % or more, 60 mol % or more. 70 mol % or more, 80 mol % or more, 90 mol % or more, 95 mol % or more, and substantially The ratio is preferably about 100 mol %. The ratio is, for example, within a range of about 30 to 100 mol %. For example, the content may be selected from 60 to 99.9 mol %, preferably 80 to 99 mol %, and more preferably 80 to 99 mol %. Preferably, the ratio is 90 to 95 mol %. If the ratio of the aryl group-containing group is too low, There is a risk of a decrease in photoelectric conversion efficiency.
[0093] In addition, when the polysilane has a non-cyclic structure such as a linear, branched, or network structure, the terminal is It may be capped or uncapped. Uncapped polysilane In the above, the terminal silicon atom is usually a methyl group, a phenyl group, or the like, in addition to the above organic group. In many cases, the alkyl group contains a hydrogen atom, a hydroxyl group, a halogen atom such as a chlorine atom, etc. In many cases, polysilanes have a hydroxyl group at the radical polymerizable group. or may be substantially free of reactive groups such as those mentioned above.
[0094] Representative polysilanes include, for example, linear polysilanes having a structural unit represented by the above formula (2a). Chain or cyclic polysilane, polysilane (network) having a structural unit represented by the formula (2b) A polysilane having a structure represented by the formulas (2a) and (2b) in combination. These polysilanes include branched or network polysilanes. In the orchid, the structural units represented by the formulas (2a) and (2b) each independently Alternatively, two or more of these may be combined. The branched or network polysilane may be represented by the following formula: It may further contain a structural unit represented by (2c).
[0095] [ka]
[0096] The shape of the polysilane may be any of linear, cyclic, branched, and network-like. It is preferable that the structure is linear, cyclic or mesh-like. The linear or cyclic structure, particularly the cyclic structure, is advantageous in terms of the conversion efficiency. Therefore, polysilanes represented by formulas (2a) and (2b) are Of the structural units, it is preferable that the polymer contains at least a structural unit represented by formula (2a).
[0097] When the polysilane contains a structural unit represented by formula (2a), the structural unit represented by formula (2a) The ratio of the position to the entire structural unit of the polysilane is, for example, in the range of about 10 mol % or more. The preferred ranges are as follows: 30 mol % or more, 50 mol % or more, and so on. 60 mol % or more, 70 mol % or more, 80 mol % or more, 90 mol % or more, and substantially It is more preferable that the ratio is 100 mol %. %, for example, from 60 to 99 mol %, preferably from 80 to 97 mol %. If the ratio of the structural unit represented by the formula (2a) is too small, the photoelectric conversion There is a risk that efficiency cannot be improved.
[0098] Specific examples of linear or cyclic polysilanes having a structural unit represented by the formula (2a) include are, for example, poly(dimethylsilane), poly(methyl-propyl-silane), poly(methyl poly(methyl-pentyl-silane), poly(dibutylsilane), Poly(dihexylsilane), (dimethylsilane)-(methyl-hexyl-silane) copolymer Poly(dialkylsilanes), such as poly(methyl-phenyl-silanes), (methyl-phenyl-silanes), Poly(alkyl-alkyl silane)-(phenyl-hexyl-silane) copolymers poly(diarylsilane); poly(diphenylsilane); (dimethylsilane)-(phenyl)-(methylphenylsilane) copolymer, (dimethylsilane)-(methyl-naphthyl-silane) copolymer, (dimethylsilane)-(methyl-naphthyl-silane) Copolymers such as (dialkylsilane)-(alkyl-aryl-silane) copolymers; (Alkyl-aryl)-(diphenylsilane) copolymers -(silane)-(diarylsilane) copolymers.
[0099] Examples of the network polysilane having the structural unit represented by the formula (2b) include polysilanes (methylsilane), poly(propylsilane), poly(butylsilane), poly(hexylsilane) Poly(alkylsilanes), such as poly(phenylsilanes); Ran) etc.
[0100] These polysilanes can be used alone or in combination of two or more. Among the silanes, linear or cyclic poly(alkyl-aryl-silanes), specifically poly Linear or cyclic poly(C1-6 Alkyl-C 6- 12 aryl-silanes; linear or cyclic poly(diarylsilanes), specifically poly (diphenylsilane) and other linear or cyclic poly(diC 6-12 Arylsilane); Linear or cyclic (alkyl-aryl-silane)-(diarylsilane) copolymers, specifically Typically linear or cyclic (methyl-phenyl-silane)-(diphenylsilane) copolymers Linear or cyclic (C 1-6 Alkyl-C 6-12 Aryl-silane)-(diC6 -12 poly(arylsilane) copolymers; network poly(arylsilane), specifically network poly Reticulated poly(C) 6-12 Arylsilanes are preferred. However, linear or cyclic poly(diarylsilanes) are preferred, and poly(diphenylsilanes) ) and other linear or cyclic poly(diC 6-10 arylsilanes) are more preferred, and deca Cyclic poly(diC)s such as phenylcyclopentasilane 6-10 Arylsilanes are particularly preferred. It is nice.
[0101] The weight average molecular weight Mw of polysilane is measured by GPC (polystyrene equivalent). For example, the range may be selected from about 300 or more. The preferred range is as follows: In terms of stages, 300~50,000, 300~25,000, 350~20,000, 400~14 000, 450-10000, 500-3000, 500-1000, and 700-1 If the weight average molecular weight is too small, the deterioration of the photoelectric conversion element cannot be effectively suppressed. If the size is too large, the solubility (or dispersibility) in the solvent decreases. This may make it difficult to fabricate the photoelectric conversion element.
[0102] The average degree of polymerization of polysilane is calculated in terms of silicon atoms (i.e., the number of silicon atoms per molecule). The average number may be selected from a wide range, for example, from about 3 to 500. The steps are 3-100, 3-50, 4-10, 5-7, 5-6, and 5. It is even more preferable that
[0103] The polysilane may be in a liquid state or a solid state at room temperature, for example, about 20° C. stomach.
[0104] Polysilanes can be produced by conventional methods, for example by dehalogenating halosilanes using magnesium as a reducing agent. A method of condensation polymerization of halogen ("Magnesium reduction method", WO98 / 29476 pamphlet) (e.g., by dehalogenation condensation polymerization of halosilanes in the presence of alkali metals (e.g., by "Ping method", J. Am. Chem. Soc., 110, 124 (1988), Macromolecules, 23, 3423 (1990), etc. A method for dehalogenating halosilanes by polar reduction (J. Chem. Soc., Chem. Commun., 1999) 161 (1990), J. Chem. Soc., Chem. Commun. 897 (1992), etc.), hydrosilation in the presence of a metal catalyst Dehydrogenative condensation polymerization of phenyls (JP Patent Publication 4-334551, etc.), biphenyl, etc. Anionic polymerization of cross-linked disilene (Macromolecules, 23, 4494 (1990), etc.) The polysilane can be obtained by a method such as ring-opening polymerization of cyclic silanes.
[0105] The proportion of polysilane in the entire polysilane layer is, for example, in the range of about 20 mass % or more. The preferred ranges are as follows: 30 to 100 mass%, 50 to 100 mass%, 100% by mass, 70~100% by mass, 90~100% by mass, 95~100% by mass, It is more preferable that the content of polysilane is substantially 100% by mass. The desorption of unstable ions such as ethylammonium cannot be suppressed, and durability cannot be effectively improved. There is a risk.
[0106] The average thickness of the polysilane layer can be selected from the range of about 1 to 100 nm, for example. 70 nm, preferably 3 to 40 nm, more preferably 5 to 20 nm, and particularly preferably 5 to 15 nm. If the average thickness of the polysilane layer is too thin, unstable isomers such as methylammonium may be easily formed. If the thickness is too thick, it may be difficult to suppress the desorption of ions and may not be possible to effectively improve durability. There is a risk that efficiency will decrease or electrical resistance will increase, resulting in a decrease in conversion efficiency.
[0107] (Electron Block Layer) The electron blocking layer is formed between the perovskite layer and the polysilane layer (directly). or indirectly laminated) on one of the perovskite layers, It is preferable that the polysilane layer is formed on at least a part of the surface of the substrate (the surface on the polysilane layer side). It seems more preferable to form it on the entire surface (especially very thinly and uniformly). The layer is determined by the energy gap and the maximum energy position of the valence band of the p-type semiconductor. This restricts the movement of electrons generated in the perovskite layer to the polysilane layer and prevents re-occurrence with holes. Therefore, the presence of an electron blocking layer can maintain the conversion efficiency for a long period of time. In some cases, this can effectively improve
[0108] The electron blocking layer may contain a p-type semiconductor, and may be a conventional p-type semiconductor, for example, The compound represented by the following formula (1b) may be included in the hole transporting material. It is also preferable to include
[0109] MX2(1b) (wherein M and X are the same as those in formula (1) above, including preferred embodiments).
[0110] Representative compounds represented by the formula (1b) include, for example, PbI2, PbBr2, PbCl2, etc., in which M is Pb in formula (1b). The compound represented by the formula (1b) may be used alone or in combination of two or more kinds. Among these compounds, PbI2, which has an energy gap of about 2.5 eV, is preferable.
[0111] The ratio of the compound represented by the formula (1b) to the entire p-type semiconductor in the electron blocking layer is For example, 50% by mass or more, preferably 90% by mass or more, substantially 100% by mass, i.e. In particular, it is more preferable that the compound is formed only from the compound represented by the formula (1b).
[0112] The electron blocking layer is preferably formed as a thin layer, and the average thickness thereof is, for example, 1 to 10 If the average thickness is too thick, the electrical resistance increases and the conversion efficiency decreases. If the thickness is too thin, the conversion efficiency or durability may not be improved effectively. .
[0113] (Hole transport layer) The photoelectric conversion element of the present invention comprises the perovskite layer, the electron blocking layer and the polysilane In addition to the layer, it is preferable to further include a hole transport layer. A hole transport layer is a layer containing a hole transport material (excluding polysilane), By stacking on the silane layer, it appears that the conversion efficiency can be effectively improved over a long period of time. do.
[0114] As the hole transport material, a conventional hole transport material can be used, and it includes inorganic compounds and organic compounds. It can be broadly divided.
[0115] Inorganic compounds include, for example, metal salts such as copper(I) thiocyanate; nickel(I) oxide; Metal oxides such as vanadium (I), vanadium (V) oxide, and copper aluminum oxide (CuAlO2); Metal iodides such as copper(I) iodide and cesium tin iodide (CsSnI3); Examples of such materials include carbon materials such as fluorine.
[0116] Organic compounds can be further classified into low molecular weight compounds and high molecular weight compounds. Examples of the phthalocyanine include phthalocyanine, naphthalocyanine, and subphthalocyanine. Anines;1,3,5-tris[2,7-(N,N-(p-methoxyphenyl)amino] Carbazoles such as [-9H-carbazol-9-yl]benzene (SGT405);2 ,5-Bis[4-(N,N-bis(p-methoxyphenyl)amino)phenyl]-3,4 -Ethylenedioxythiophene (H101), 2,3,4,5-tetrakis[4-(N, Thiophene (H111) and other thiophenes such as N-bis(p-methoxyphenyl)amino)phenyl]thiophene (H111) 2,6,14-tris[5'-(4-(N,N-bis(p-methoxyphenyl) (amino)phenyl)-thiophen-2'-yl]triptycene (T103) Liptycenes; spirobifluorenes such as the compound represented by formula (3) described below. Can be obtained.
[0117] As the polymer compound, for example, poly(3-hexylthiophene-2,5-diyl) ( P3HT), poly[N-9'-heptadecanyl-2,7-carbazole-alt-5,5 -(4',7'-di-2-thienyl-2',1',3'-benzothiadiazole)](P CDTBT), poly[N-9'-heptadecanyl-2,7-carbazole-alt-3, 6-Bis(thiophen-5-yl)-2,5-dioctyl-2,5-dihydropyrrolo[3 ,4]pyrrole-1,4-dione] (PCBTDPP), poly[2,6-(4,4-bis -(2-Ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b']dithio phenyl)-alt-4,7-(2,1,3-benzothiadiazole)](PCPDTBT) Polythiophenes such as poly[bis(phenyl-4-yl)-(2,4,6-trimethyl Poly[bis(phenyl-4-yl)-(4-butyl)amine](PTAA), triarylamines such as poly[9 ,9-Dioctylfluorene-co-bis-N,N'-(4-butylphenyl)-bis- Polyfluorenes such as N,N'-phenyl-1,4-phenylenediamine (PFB) etc.
[0118] These hole transport materials may be used alone or in combination of two or more kinds. Among these hole transport materials, spirobifluorenes, for example, those represented by the following formula (3) Compounds are preferred.
[0119] [ka]
[0120] (In the formula, Z 1 ~Z 8 each independently represents an arene ring; R 4a ~R 4h Each is unique represents an alkoxy group, and k1 to k8 each independently represent an integer of 0 or more.
[0121] In the formula (3), Z 1 ~Z 8 As an aromatic hydrocarbon ring (arene ring) represented by For example, a monocyclic aromatic hydrocarbon ring such as a benzene ring (monocyclic arene ring), a polycyclic aromatic Examples of polycyclic aromatic hydrocarbon rings include aromatic hydrocarbon rings (polycyclic arene rings). For example, condensed polycyclic aromatic hydrocarbon rings (condensed polycyclic arene rings), ring-assembled aromatic hydrocarbon rings (ring assembly arene ring), etc.
[0122] Examples of the fused polycyclic arene ring include a fused bicyclic arene ring and a fused tricyclic arene ring. Examples of the fused bicyclic arene ring include fused bicyclic to tetracyclic arene rings such as , for example, fused bicyclic C rings such as naphthalene rings 10-16 arene rings, etc. Examples of the tricyclic arene ring include an anthracene ring and a phenanthrene ring. Preferred fused polycyclic arene rings include fused polycyclic arene rings such as naphthalene rings and anthracene rings. Polycyclic C 10-16 arene rings, more preferably fused polycyclic C 10-14 Alley A naphthalene ring is particularly preferred.
[0123] Examples of the ring-assembled arene ring include a biarene ring and a terarene ring. Examples of the ring include a biphenyl ring, a binaphthyl ring, a phenylnaphthalene ring, and the like. C6-12 arene rings, and phenylnaphthalene rings include 1-phenylnaphthalene. Examples of the terarene ring include the following: For example, terphenylene rings and other terphenylene rings 6-12 arene rings. The assembled arene ring is 6-10 An arene ring is exemplified, and a biphenyl ring is particularly preferred.
[0124] These rings Z 1 ~Z 8 Among them, C rings such as benzene ring, naphthalene ring, and biphenyl ring 6- 12 Arene rings are preferred, and C such as benzene rings are preferred. 6-10 An arene ring is more preferred. A benzene ring is particularly preferred. 1 ~Z 8 may be different from each other, Usually, they are the same. 1 ~Z 8 The bond position with the nitrogen atom in It's fine.
[0125] In the formula (3), R 4a ~R 4h The alkoxy group represented by the formula: , ethoxy group, propoxy group, n-butoxy group, i-butoxy group, s-butoxy group, t- Linear or branched C such as butoxy group 1-6 Alkoxy groups are preferred. is linear or branched C 1-4 C1 such as an alkoxy group, more preferably a methoxy group -2 It is an alkoxy group.
[0126] base R 4a ~R 4h The substitution numbers k1 to k8 of the ring Z 1 ~Z8 You can choose according to the type of The range may be an integer of about 0 to 7, and the preferred range is an integer of 0 to 6 in the following order: is an integer of 0 to 4, an integer of 0 to 2, more preferably 0 or 1, and particularly preferably 1. It is preferable. k1 to k8 may be different from each other, or may be the same. When k1 to k8 are 2 or more, the corresponding 2 or more groups R 4a ~R 4h The types are the same They may be one or different.
[0127] base R 4a ~R 4h The substitution position of is ring Z 1 ~Z 8 Positions other than the position where the nitrogen atom is bonded to As long as the ring is, there is no particular limitation. For example, the ring Z 1 ~Z 8 is a benzene ring, k1 to k8 are 1 If present, the group R 4a ~R 4h The substitution position of is ring Z 1 ~Z 8 With respect to the bonding position with the nitrogen atom The position may be any of o-position, m-position, and p-position, and preferably m-position or p-position. It may be at the -position, more preferably at the p-position.
[0128] In the formula (3), the four nitrogen atoms are connected to four groups forming a spirobifluorene skeleton. The positions of the nitrogen atoms bonded to the benzene ring are not particularly limited. For example, Any one of the 2-4 positions and any one of the 5-7 positions of the fluorene ring position, any one of the 2' to 4' positions, and any one of the 5' to 7' positions and the four nitrogen atoms are bonded to the 2,2' positions of the spirobifluorene ring. ,7,7' positions are preferred.
[0129] Representative examples of the compound represented by formula (3) include the following: Ring Z 1 ~Z 8 is a benzene ring, k1 to k8 are 1, 2,2',7,7'-tetrafluoroethylene]-9,9'-spirobifluorenes, for example, Kis-[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene Spiro-OMeTAD, 2,2',7,7'-tetrakis-[N-(4-methoxyphenyl )-N-(3-methoxyphenyl)-amino]-9,9'-spirobifluorene, 2,2 ',7,7'-Tetrakis-[N-(4-methoxyphenyl)-N-(2-methoxyphenyl) nyl)-amino]-9,9'-spirobifluorene, 2,2',7,7'-tetrakis- [N,N-bis(4-ethoxyphenyl)amino]-9,9'-spirobifluorene, etc. Tetrakis[bis(C 1-4 Alkoxyphenyl)amino]-9,9'-spirobiphenyl Oren, etc.
[0130] These compounds represented by the formula (3) may be used alone or in combination of two or more. Among these compounds represented by the formula (3), tetracycline such as Spiro-OMeTAD can be used. Rakis [bis (C 1-2 Alkoxyphenyl)amino]-9,9'-spirobifluorene It is preferable that the compound represented by the formula (3) is a commercially available product. good.
[0131] The ratio of the compound represented by the formula (3) to the entire hole transport material in the hole transport layer is as follows: For example, the range may be selected from about 10% by mass or more, and the preferred range is as follows: Generally, 30% by mass or more, 50% by mass or more, 70% by mass or more, 90% by mass or more, 95% by mass It is more preferable that the ratio is substantially 100% by mass or more. 100% by mass, preferably 60 to 99% by mass, and more preferably 80 to 95% by mass. This is also fine.
[0132] The hole transport layer does not necessarily contain any additive in addition to the hole transport material. If necessary, the composition may further contain conventional additives such as dopants. (or p-type dopants) include, for example, metal compounds; and non-metallic compounds such as 7,7,8,8-tetracyanoquinodimethane. The metal compound is, for example, lithium bis(trifluoromethylsulfonyl)imide. Metal salts such as hexafluoroammonium tetrachloride (Li-TFSI); tris(p-bromophenyl)ammonium hexafluoroammonium Chloroantimonate, tris(2-(1H-pyrazol-1-yl)pyridine)cobalt (III) tris[bis(trifluoromethylsulfonyl)imide], molybdenum tris Metal complexes such as [1,2-bis(trifluoromethyl)ethane-1,2-dithiolene]; Metal chlorides such as tin(IV) chloride, antimony(V) chloride, and iron(III) chloride; tin oxide Examples include metal oxides such as tin(VI).
[0133] When a hole transport material is combined with an additive, the proportion of the additive, such as a dopant, is adjusted to the hole transport ratio. For example, 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, based on 100 parts by mass of the total amount of the feed material. The content is preferably 5 to 15 parts by mass.
[0134] The thickness (average thickness) of the hole transport layer may be selected, for example, from the range of about 5 to 300 nm. The preferred ranges are as follows: 10 to 200 nm, 20 to 100 nm, 30 If the average thickness of the hole transport layer is too thin, the holes cannot move efficiently and the If the thickness is too thick, the electrical resistance increases and the conversion efficiency decreases. There it is.
[0135] (First electrode) The first electrode is a transparent substrate, for example, an inorganic material such as glass, a methacrylic resin, or a polycarbonate. For example, FTO (Fluo Transparent films such as rine-doped tin oxide, ITO (indium tin oxide), and ZnO (zinc oxide) A transparent electrode formed by coating a transparent conductive metal oxide. The deposition method is not particularly limited, and examples thereof include deposition such as vacuum deposition and coating. Among these, FTO is preferred from the viewpoint of heat resistance.
[0136] The metal oxide may also be formed into a desired pattern by etching or the like. Furthermore, functional layers such as an anti-reflection layer and a hard coat layer are formed on the other surface of the transparent substrate. The first electrode may be an anode, but is usually a cathode in many cases.
[0137] The average thickness of the transparent conductive metal oxide coating film in the first electrode is, for example, 5 to 100 nm. The range can be selected from about 2000 nm, and the preferred range is 100 to 2000 nm in the following order: 1500nm, 500~1200nm, 800~1000nm. The average thickness is too thick. If the thickness is too thin, the weight of the photoelectric conversion element may increase, and if the thickness is too thin, the durability may decrease. In addition, the average thickness of the transparent substrate in the first electrode can be selected according to the material. The thickness is generally 0.1 to 3 mm, and preferably 1 to 2 mm.
[0138] (Electron transport layer (ETL)) The electron transport layer efficiently transports electrons, improving properties such as conversion efficiency and improving the perovskite structure. This can prevent the layer, polysilane layer, hole transport layer, etc. from coming into contact with the cathode and shorting out. The transport layer is typically formed on the metal oxide coated surface of the first electrode (or the second electrode in the case of an inverted structure). The electron transport material is densely (not porously) deposited on one side of the electrode (one side of the electrode 2). There are.
[0139] Examples of the electron transport material include titanium oxide (IV), zinc oxide (II), and strontium oxide. Metal oxides such as zinc(IV), phenyl-C61-butyric acid methyl ester (
[60] PCBM) and other fullerenes. These electron transport materials may be used alone or in combination of two or more. Metal oxides are preferred, and among these, titanium oxide (IV) and zinc oxide (II) are preferred. Titanium(IV) oxide is particularly preferred.
[0140] The electron transport layer may be doped with other atoms. In this case, an atom having a higher valence than the metal atom in the metal oxide may be doped, for example, In titanium oxide (IV), vanadium (V), niobium (Nb), tantalum (Ta), etc. Pentavalent atoms may be doped, for example, aluminum (Al) and gallium (Ga) in zinc oxide (II). Doping with a trivalent atom such as gallium (Ga) or indium (In) may also be used.
[0141] The average thickness of the electron transport layer may be selected, for example, from the range of about 5 to 100 nm. The preferred ranges are as follows: 10-80 nm, 20-60 nm, and 30-50 nm. If the average thickness is too thick, the electrical resistance may increase, and if it is too thin, the electrons may not be transported efficiently. There is a risk of not being able to move around well.
[0142] (Second electrode) The second electrode is usually gold (Au) adjacent to the hole transport layer (or electron transport layer in the case of an inverted structure). metals such as silver (Ag), copper (Cu), and aluminum (Al); The electrodes are made of metal or carbon, and are made of conductors with a charge function of 5.2 eV or less. Of the materials (or electrode forming materials), Au is preferred. The second electrode is Correspondingly, it may be a cathode, but is usually an anode.
[0143] The average thickness of the second electrode may be selected from the range of, for example, about 100 to 500 nm. The preferred ranges are as follows: 120 to 300 nm, 150 to 250 nm, 18 If the average thickness is too thick, the manufacturing efficiency may decrease. If it is too long, there is a risk that current will not be collected efficiently.
[0144] [Production method and characteristics of photoelectric conversion element] The photoelectric conversion element is a perovskite compound for forming a compound having a perovskite structure. A polysilane layer is deposited on one side of the film containing the perovskite precursor (or the perovskite precursor layer). A polysilane layer forming process in which a preliminary laminate (primary laminate) is formed by The preliminary laminate (primary laminate) obtained in the above step is heat-treated to form the perovskite layer, the electron block, A heat treatment step to form a laminate (secondary laminate or laminate structure) including the polysilane layer and the polysilane layer. (or a perovskite crystal growth process). Prior to the formation of the perovskite layer, a film containing a perovskite precursor (perovskite precursor layer) is It is preferable to include a perovskite precursor film formation step.
[0145] (Perovskite precursor film formation process) In the perovskite precursor film formation process, a compound having a perovskite structure is formed. As long as a film (or a perovskite precursor layer) containing a perovskite precursor for The method is not particularly limited, and the layer may be formed by a conventional method such as immersion or vapor deposition, and is preferably formed by such a method. A perovskite precursor (perovskite precursor compound) and a solvent (or dispersion medium) are mixed. The perovskite layer is formed by coating a precursor solution (or dispersion) containing Usually, the electron transport layer formed in the electron transport layer forming step described later or the porous portion forming step It is laminated on the formed porous portion.
[0146] In addition, the film containing the perovskite precursor (or the perovskite precursor layer) may include the following: In addition to the perovskite precursors, the perovskite compounds corresponding to the precursors (AMX 3) may be partially contained, for example, by the air blow method described later. The perovskite compound may be included.
[0147] The perovskite precursor contained in the perovskite layer precursor solution is, for example, A precursor corresponding to the perovskite compound represented by formula (1), i.e., the following formula (1a): and (1b).
[0148] AX (1a) MX2(1b) (In the formula, A, M and X are the same as those in the above formula (1), including preferred embodiments thereof.)
[0149] Representative compounds represented by the formula (1a) include, for example, CH3NH3I (or MAI), CH3NH3Br (or MABr), CH3NH3Cl (or MACl) , CH3CH2NH3I (or EAI), CH3CH2NH3Br (or EABr) In the formula (1a) such as 1-6 Alkylammonium compounds; HC(NH 2) Formula (1a), such as 2I (or FAI), HC(NH2)2Br (or FABr) In A is C 1-6 Amidinium compounds; A is an alkali metal, such as KI, KBr, etc. Among these compounds, MAI, MABr, EA Br, FAI, FABr, and KI are preferred, and MAI, FAI, and KI are more preferred.
[0150] Representative compounds represented by the formula (1b) include, for example, PbI2, PbBr2, PbCl2, etc., in which M is Pb in formula (1b). Of these compounds, PbI2 and PbCl2 are preferred, with PbCl2 being more preferred.
[0151] The compounds represented by the formulas (1a) and (1b) are the target compounds represented by the formula (1). Depending on the type of perovskite compound, they can be used alone or in combination of two or more. Therefore, the compounds represented by the formulas (1a) and (1b) can be used as the By combining them in the desired ratio, the stoichiometric ratio can be obtained. Alternatively, the perovskite compound described in the above (Perovskite layer) section may be prepared. .
[0152] The ratio of the compound represented by the formula (1a) to the compound represented by the formula (1b) is, for example, For example, the molar ratio of the former to the latter is 1 / 0.9 to 1 / 1.1, or substantially equimolar (1 / 1). However, in the heat treatment step described later, the perovskite crystals are formed by heat treatment at a high temperature. In the case of growth, the molar ratio of the former to the latter is substantially about 3 / 1, for example, 3 / 0.9 to 3 / About 1.1, preferably 3 / 0.95 to 3 / 1.05, and more preferably 3 / 1 to 3 / 1.03. It is more preferable to use a compound represented by the formula (1b) for 3 moles of the compound represented by the formula (1a). When the ratio of the compound represented by the formula (1a) is adjusted to be slightly more than 1 mole, In cases where the compound to be treated contains an alkali metal halide such as KI, the heat treatment described below In the case of heat treatment at high temperatures, the above-mentioned formula may be easily formed as an electron blocking layer. Compounds represented by (1b) include those in which X is chlorine (Cl), such as PbCl2 (M In other words, when heat treatment is performed at high temperatures, the reaction is represented by the following reaction formula (4): Thus, the perovskite compound (AMX3) represented by the above formula (1) is prepared.
[0153] 3AX + MCl2→ AMX3+ 2ACl↑ (4) (In the formula, A, X and M are the same as those in the above formula (1), including preferred embodiments.)
[0154] As is clear from the formula (4), the perovskite represented by the formula (1) Compound (AMX3) corresponds to compounds AX and MCl2 (or A, X and By appropriately selecting the types and ratios of ions (represented by M and M), the above The perovskite compound described in the above section (Perovskite Layer) can be prepared.
[0155] In addition, in the right side of the formula (4), the compound (2ACl) that is generated as a gas is The monovalent cation A is preferably methylammonium. For a total of 3 moles of compound (AX) represented by the formula (1), It is preferred to use at least a 2 molar ratio of the substances.
[0156] Examples of the solvent (or dispersion medium) include lactones and amides. For example, C3 such as γ-butyrolactone, δ-valerolactone, and ε-caprolactone -7 Examples of the amides include N,N-dimethylformamide. Dimethyl acetamide (DMF), N,N-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone Dong (NMP) and others.
[0157] These solvents can be used alone or in combination of two or more. Among the solvents, γ-butyrolactone and DMF are preferred, and amides such as DMF are more preferred. I wish.
[0158] The ratio of the solvent is 100% by weight of the compounds represented by the formulas (1a) and (1b). For example, 10 to 1000 parts by mass, preferably 50 to 500 parts by mass, more preferably 10 to 1000 parts by mass, more preferably 50 to 500 parts by mass, The amount is preferably 100 to 200 parts by mass.
[0159] The compound represented by the formula (1a), the compound represented by the formula (1b) and the solvent are The mixture may be mixed while being heated to a temperature not higher than the boiling point of the solvent. The heating temperature is, for example, 40 to 80° C. The mixing temperature is preferably 50 to 70° C. The mixing time is, for example, 1 to 48 hours, preferably 12 to 36 hours. The perovskite layer precursor solution thus prepared is The solvent may be applied to the electron transport layer while being heated to a temperature equal to or lower than the boiling point of the solvent. The temperature is usually 50 to 90°C, and preferably 60 to 80°C.
[0160] The perovskite layer precursor solution may be prepared and coated at once, but it is recommended to coat the porous portion with the solution at once. From the viewpoint of efficient impregnation or immersion, it is preferable to coat the material in a number of separate steps. The number of coating times is, for example, 1 to 5 times, preferably 2 to 4 times, and more preferably 3 times. be.
[0161] The perovskite layer precursor solution can be coated by a conventional coating method, for example, by spray coating. Pin coat method, doctor blade method, screen printing method, and other coating or printing methods, vacuum steaming A deposition method such as a vapor deposition method can be used, and a spin coating method is preferred.
[0162] In addition, when forming a film containing a perovskite precursor by spin coating, the productivity is improved. From the viewpoint of this, we decided to use an air blower ( As described above, the perovskite layer precursor solution is preferably mixed. If multiple coatings are applied, air blowing may be used for each coating. However, only the latter half, for example, when coating with three spin coats, the second and third coats It is preferable to carry out the process by air blowing.
[0163] In the air blowing method, the temperature of the air blown is in the range of, for example, 50 to 140°C. The preferred ranges are as follows: 70 to 120° C., 80 to 10 The temperature is preferably 0°C, and more preferably 85 to 95°C.
[0164] The perovskite precursor film was formed in an inert gas atmosphere such as nitrogen gas as in the conventional method. Although the process may be carried out in air, in the present invention, the perovskite precursor film formation process is carried out in an air atmosphere. Since the conversion efficiency can be maintained high or improved for a long period of time, productivity can be effectively improved. Cut.
[0165] (Polysilane layer formation process) In the polysilane layer formation step, polysilane is applied to one side of the film containing the perovskite precursor. A polysilane layer containing silane is laminated to form a preliminary laminate (primary laminate). The layers may be formed by a conventional method such as immersion or vapor deposition. A polysilane layer forming solution (or dispersion liquid) containing polysilane and a solvent (or dispersion medium) is applied to the coating. The method of rinsing is preferred.
[0166] Examples of the solvent (or dispersion medium) include hydrocarbons, halogenated hydrocarbons, and alkoxysilanes. ethers, glycol ethers, glycol ether acetates, ketones , esters, carbonates, carboxylic acids, nitriles, amides, sulfoxides Examples of the solvent include water, water, and mixtures thereof.
[0167] Examples of the hydrocarbons include aliphatic hydrocarbons such as hexane, cyclohexane, etc. and aromatic hydrocarbons such as toluene and xylene.
[0168] Examples of halogenated hydrocarbons include chlorinated hydrocarbons. Examples of hydrocarbons include dichloromethane, chloroform, and 1,2-dichloroethane. Chlorinated aliphatic hydrocarbons such as chlorobenzene and dichlorobenzene, and chlorinated aromatic hydrocarbons such as chlorobenzene and dichlorobenzene. Hydrocarbons and the like.
[0169] Examples of alcohols include methanol, ethanol, 2-propanol, and n-butyl alcohol. C such as ethanol and t-butanol 1-6 Alkane monool, ethylene glycol, etc. C 2-4 Alkanediols and the like.
[0170] Examples of the ethers include chain ethers such as diisopropyl ether, tetraethyl ether, Examples of the ether include cyclic ethers such as hydrofuran.
[0171] Examples of glycol ethers include cellosolves such as methyl cellosolve; Carbitols such as ethyl carbitol, triethylene glycol monomethyl ether, (Poly)C such as propylene glycol monomethyl ether 2-4 Alkylene glycol No.C 1-4 Alkyl ethers; ethylene glycol dimethyl ether, dipropylene glycol (Poly)C such as cholesteryl ether 2-4 Alkylene glycol di-C 1-4 Alki Examples include ether.
[0172] Examples of glycol ether acetates include cellosolve acetates and carbohydrate acetates. Tol acetates, propylene glycol monomethyl ether acetate, dipropylene (Poly)C such as ethylene glycol monobutyl ether acetate 2-4 Alkylene Glycol Rumono C 1-4 Alkyl ether acetates, etc. Cellosolve acetates Examples of the C 1-4 Alkyl Cellosolve Ace Examples of carbitol acetates include methyl carbitol. C such as ethyl acetate 1-4 Alkyl carbitol acetates and the like.
[0173] Examples of ketones include chain ketones such as acetone and methyl ethyl ketone; and cyclic ketones such as hexanone.
[0174] Examples of esters include acetate esters such as ethyl acetate, and lactates such as methyl lactate. Esters and the like.
[0175] Examples of carbonates include chain carbonates such as dimethyl carbonate, ethylene carbonate, propylene carbonate, and other cyclic carbonates. .
[0176] Examples of the carboxylic acids include acetic acid and propionic acid.
[0177] Examples of nitriles include acetonitrile and propionitrile.
[0178] Examples of amides include N,N-dimethylformamide and N,N-dimethylacetamide. amide, N-methyl-2-pyrrolidone, etc.
[0179] The sulfoxides include, for example, dimethyl sulfoxide.
[0180] These solvents can be used alone or in combination of two or more. Among the solvents, halogenated hydrocarbons such as chlorobenzene are preferred. The concentration of the polysilane in the solution (or dispersion) is, for example, 5 to 50 mg / mL, preferably The concentration is 10 to 30 mg / mL, and more preferably 15 to 25 mg / mL.
[0181] As a method for coating the polysilane layer forming solution, for example, As a method for coating the precursor solution, the conventional coating method exemplified above can be used. The pin coating method is preferable. The spin coating of the polysilane layer forming solution is preferably performed on the perovskite When forming a film containing a precursor by spin coating (if spin coating is performed multiple times, When spin-coating the perovskite layer, the precursor solution is dropped and after a certain time has elapsed, e.g. For example, after 30 to 60 seconds, the polysilane forming solution may be added dropwise. The spin coating of the silane forming solution is also preferably carried out by the air blow method described above.
[0182] The polysilane layer forming process may be carried out in an inert gas atmosphere such as nitrogen gas. In the present invention, the conversion efficiency can be maintained high or improved for a long period of time even in an air atmosphere. This effectively improves productivity.
[0183] (Heat treatment process (or crystal growth process)) In the heat treatment process, the preliminary laminate (primary laminate) obtained in the polysilane layer formation process is heat treated. A laminate including a perovskite layer, an electron blocking layer and a polysilane layer (secondary laminate) In particular, perovskite is formed by heat treatment, especially at high temperatures. The perovskite layer is formed by growing perovskite crystals in a film containing a perovskite precursor. However, during the heat treatment, the surface of the perovskite precursor layer (the interface with the polysilane layer) is not uniform. In the thin region, the p-type semiconductor compound MX2 is formed minutely from the perovskite layer precursor. It appears that the electron blocking layer can be formed by the above heat treatment. During this process, A in the compound represented by the above formula (1a), such as methylammonium, is slightly desorbed. X in the compound represented by formula (1a) and X in the compound represented by formula (1b) The compound MX2 is generated by reacting with M (the compound used to form the perovskite precursor layer). It is presumed that the precursor is generated separately from the polysilane layer.
[0184] The heat treatment temperature for growing perovskite crystals is about 80 to 100°C, as in the past. However, in the present invention, the polysilane layer is laminated on the film containing the perovskite precursor. The heat resistance of the layer is high, so durability can be effectively improved even when heat treated at high temperatures. The treatment temperature may be selected from the range of, for example, about 140 to 250° C., and a preferred range is The following temperature ranges are available: 150-240℃, 160-230℃, 170-220℃, 175℃ If the heat treatment temperature is too low, the electron blocking layer cannot be efficiently If the temperature is too high, the perob The skite crystals may decompose and the productivity may decrease. For example, it may be about 1 to 60 minutes, preferably 2 to 30 minutes, and more preferably 3 to 10 minutes. minutes.
[0185] The heat treatment for growing the perovskite crystals was carried out in the same manner as in the past, using nitrogen gas, etc. Although the heat treatment may be carried out in an inert gas atmosphere, the heat treatment step of the present invention may be carried out in an air atmosphere. Since the conversion efficiency can be maintained high or improved for a long period of time, the productivity can be effectively improved.
[0186] (Hole transport layer forming process) The method of the present invention further includes a hole transport layer forming step of laminating a hole transport layer on the polysilane layer. It is preferable to
[0187] In the hole transport layer forming step, the polysilane of the laminate (secondary laminate) formed in the heat treatment step is The hole transport material such as the compound represented by formula (3) and a solvent (or a dispersion medium) are applied to the surface of the insulating layer. A hole transport layer forming solution (or dispersion) containing a hole transport solvent is coated on the substrate. A transfer layer is formed.
[0188] As the solvent (or dispersion medium), for example, the solvents exemplified in the polysilane layer forming step may be used. These solvents may be used alone or in combination of two or more. Of these solvents, halogenated hydrocarbons such as chlorobenzene are preferred. The ratio of the solvent is, for example, 500 to 2000 parts by mass with respect to 100 parts by mass of the total amount of the hole transport material. The amount is preferably 1000 to 1500 parts by mass.
[0189] The hole transport layer forming solution may contain, if necessary, additives such as those exemplified in the section on the hole transport layer. For example, a dopant such as Li-TFSI may be included, and the ratio of these additives is The ratio and preferred embodiments may be the same as those described in the section on the hole transport layer. The additives such as nitrile and the like are preferably used in the same solvent as the hole transport material, for example, acetonitrile and the like. The compound may be added after being dissolved or dispersed in tolyl or the like.
[0190] In addition, the hole transport layer forming solution can improve the open circuit voltage by changing the quasi-Fermi level. Therefore, if necessary, it may contain amines such as heterocyclic amines and tertiary amines. Examples of heterocyclic amines include C amines such as 4-t-butylpyridine. 1-6 Alkylpyridin Examples of tertiary amines include triethylamine and other tri-C 1- 6 Tri-C such as alkylamines and triethanolamine 1-6 Alkanolamines, etc. These amines can be used alone or in combination of two or more. Among these amines, heterocyclic amines such as 4-t-butylpyridine are preferred. The ratio of the amines is, for example, 0.1 to 10 parts by volume relative to 100 parts by volume of the solvent, preferably The volume ratio is preferably 1 to 5 parts by volume. The volume ratio is determined under room temperature of 1 atmosphere and 25° C. It may also be the volume at room temperature.
[0191] The hole transport layer forming solution may be prepared while being heated. The heating temperature is, for example, 50 to 100 The temperature is preferably 60 to 80° C. The hole transport layer forming solution is In order to prevent the decomposition of the hole transport material, such as the compound It's okay.
[0192] The hole transport layer forming solution can be coated, for example, by The conventional coating method exemplified as the coating method for the body solution can be used. The coating method is preferred.
[0193] The hole transport layer formation process is carried out in an inert gas atmosphere such as nitrogen gas as in the conventional method. However, in the present invention, the conversion efficiency can be maintained high for a long period of time even in an air atmosphere. This can improve productivity effectively.
[0194] (Other processes) The method for producing a photoelectric conversion element of the present invention further includes a step of forming an electron transport layer and a step of forming a porous portion. , a step of forming a second electrode, etc.
[0195] (Electron transport layer formation process) In the electron transport layer forming step, the electron transport material or its precursor and a solvent (or a dispersion medium) are An electron transport layer precursor solution (or dispersion) containing the above is coated to form an electron transport layer. The coating is applied when the photoelectric conversion element is a nanostructure type or a planar heterojunction type. In the case of an inverted structure, the conductive metal oxide-coated surface of the first electrode is coated with a second The electrode may be coated with the
[0196] The electrode to be coated, preferably the first electrode, is coated with a solution of the electron transport layer precursor. A washing treatment may be carried out before coating. The washing method is not particularly limited, and for example, Immerse in ketones such as acetone or alcohols such as methanol, then ultrasonically clean and rinse with nitrogen. Drying under inert gas such as gas or rare gas; UV-ozone treatment; A combination method is also possible.
[0197] The precursor of the electron transport material may be any of the electron transport materials exemplified in the section on the electron transport layer. Compounds that can be used include, for example, titanium oxide (IV) precursors and zinc oxide (II) precursors. Titanium(IV) oxide precursors include, for example, titanium diisopropoxide bis(acetate). titanium complexes such as titanium(IV) tetraisopropoxide; Examples of zinc(II) oxide precursors include zinc carbonate. Examples include:
[0198] As the solvent (or dispersion medium), for example, the solvents exemplified in the polysilane layer forming step may be used. These solvents may be used alone or in combination of two or more. Among these solvents, C such as n-butanol is 1-5 Alkane monool etc. are preferred.
[0199] The concentration of the electron transport material or its precursor in the electron transport layer precursor solution is, for example, 0 The concentration is 0.01 to 1 M, preferably 0.1 to 0.4 M. In addition, the electron transport layer is In order to form a dense and tight bond to the electrode, two or more solutions with different concentrations are prepared. Alternatively, solutions may be coated in the order of increasing concentration.
[0200] As a method for coating the electron transport layer precursor solution, for example, As a method for coating the precursor solution, the conventional coating method exemplified above can be used. The pin coating method is preferred.
[0201] After coating, a heat treatment may be carried out to remove the solvent. The heating temperature may be, for example, The temperature is generally 80 to 200° C., and preferably 100 to 150° C. In addition, the metal oxide is To form a product, a heat treatment may be further performed at a high temperature, and the heating temperature is The temperature can be selected depending on the type, and is, for example, 300 to 800°C, preferably 400 to 600°C.
[0202] (Porous part formation process) If the photoelectric conversion element is a nanostructure type, before coating with the perovskite layer precursor solution The porous portion (first perovskite compound) is provided for contacting the perovskite compound over a wide surface area. The porous portion of the skite layer may be formed in the electron transport layer. A porous portion forming solution containing a molecular compound, water, an organic compound, and a surfactant is applied to the surface of the substrate. The film is formed by subjecting the film to a heat treatment.
[0203] As the metal oxide, the porous oxides exemplified in the first perovskite layer section are The metal oxides are the same as those shown above, including preferred embodiments. etc. may be used.
[0204] Examples of the polymer compound include water-soluble polymer compounds. Polyethylene glycol, polyvinyl alcohol, poly(meth)acrylic acid derivatives, cellulosic Examples of the poly(meth)acrylic acid derivatives include poly( Examples of the cellulose include acrylic acid or its salts, and poly(meth)acrylamide. Examples of the cellulose derivatives include carboxymethylcellulose or its salts, hydroxypropylcellulose, and the like. Examples include cellulose ethers such as pyrocellulose. The weight average molecular weight is, for example, 10,000 to 30,000, preferably 15,000 to The ratio of the polymer compound is, for example, 1 to 100 parts by mass of the metal oxide. The content is from 5 to 30 parts by mass, and preferably from 5 to 15 parts by mass.
[0205] The water is preferably ultrapure water. The ratio of water to 100 parts by mass of metal oxide is, for example, For example, it is 100 to 1000 parts by mass, and preferably 300 to 700 parts by mass.
[0206] Examples of organic compounds include complex-forming organic compounds such as acetylacetone. The ratio of the organic compound is, for example, 0.1 to 10 parts by volume relative to 100 parts by volume of water. The volume ratio is preferably 1 to 5 parts by volume. The volume ratio is determined at about 1 atmospheric pressure and 25° C. It may be the volume at room temperature.
[0207] Examples of the surfactant include nonionic surfactants, anionic surfactants, cationic surfactants, and the like. Examples of the surfactant include anionic surfactants and amphoteric surfactants, and nonionic surfactants are preferred. Examples of anionic surfactants include polyethylene glycol-(t-octylphenyl Polyoxyethylene (C) ethers 6-20 Alkyl-phenyl) ethers, etc. The ratio of the surfactant to 100 parts by volume of water is, for example, 0.05 to 5 parts by volume. The volume in the above ratio is 1 atm, 25 The volume may be at room temperature of about °C.
[0208] The porous portion forming solution is prepared by mixing a metal oxide, a polymer compound, and water, stirring the mixture, and then Alternatively, an organic compound and a surfactant may be further added to the mixture and stirred to prepare the dispersion. In order to remove air bubbles from the solution, the solution is left to stand for 1 hour to 2 days, preferably 12 hours to 1 day, after preparation. You may do so.
[0209] As a method for coating the porous portion forming solution, for example, As a solution coating method, the conventional coating method exemplified above can be used, and spin coating can be used. The coating method is preferred.
[0210] The heat treatment temperature after coating with the porous portion forming solution is, for example, 300 to 800° C. The temperature is preferably 400 to 600° C. The porous portion thus obtained is subjected to the above-mentioned perforation treatment. The perovskite layer precursor solution is coated (or The perovskite precursor can be formed by a method comprising the steps of:
[0211] (Second electrode forming process) In the second electrode formation step, a conductor such as a metal or carbon as exemplified in the second electrode section is used. The second electrode is formed by deposition, for example, vacuum deposition. In the case of the nanostructure type or the planar heterojunction type, the hole transport layer formed in the hole transport layer forming step In the case of an inverted structure, the electron transport layer may be applied to the electron transport layer formed in the electron transport layer forming step. .
[0212] After laminating each layer, if necessary, wiring can be connected or a cover can be attached to complete the photoelectric conversion. A conversion element may be fabricated.
[0213] (Photoelectric conversion element characteristics) The photoelectric conversion element obtained by the present invention exhibits high durability and can be used or stored in the atmosphere. Therefore, the conversion efficiency can be maintained high or improved for a long period of time even after a long period of exposure to the atmosphere. Conversion efficiency after η x The higher the conversion rate, the more preferable. For example, the conversion rate may be about 8% or more. Efficiency η x For example, it may be about 8 to 18%, preferably 10 to 15%, and more preferably Preferably, it may be about 12 to 14%. In addition, after a long period of time in the atmosphere (or after the above-mentioned change), Conversion efficiency η x Short circuit current density J sc-xThe higher the better, for example 5 mA cm -2 Generally, the short circuit current density J sc-x For example, 15 to 30 mA cm -2 , preferably 18 to 25 mA cm -2 , and more preferably 20 to 23 m A cm -2 After a long period of time in the atmosphere (or the conversion efficiency η x measurement Open circuit voltage V oc-x The higher the voltage, the more preferable it is. For example, it may be about 0.5 V or more. Usually, the open circuit voltage V oc-x is, for example, 0.8 to 1.2 V, preferably 0.9 to 1 V The conversion efficiency η x , short circuit current density J sc-x and open circuit voltage V oc-x is a long-term condition, such as four weeks or more after the photoelectric conversion element is manufactured. The higher the value, the more preferable it is. Usually, for example, after 5 to 50 weeks, preferably after 8 to 30 weeks. The value may be the value after about 20 to 25 weeks have elapsed.
[0214] The initial conversion efficiency η0 of the photoelectric conversion element is preferably as high as possible. For example, Ordinarily, the initial conversion efficiency η0 is, for example, about 1 to 20%. It may be about 5 to 18%, preferably about 8 to 15%. The short circuit current density J sc-0 The higher the better, for example, 5 mA cm -2 Generally, the short circuit current density J sc-0 For example, 5 to 3 0mA cm -2 , preferably 10 to 25 mA cm -2 , more preferably 15 to 22 mA cm -2 The initial open circuit voltage V oc-0 The higher the better For example, the initial open circuit voltage V oc-0 teeth For example, the voltage may be about 0.3 to 1.2 V, and preferably about 0.8 to 1 V. So, the initial conversion efficiency η0 and short circuit current density J sc-0 , open circuit voltage V oc-0 Low However, because it is stable over a long period of time, the characteristics may improve gradually.
[0215] In this specification and claims, the conversion efficiency, short circuit current density, and open circuit voltage are determined by the illuminance. 100mWcm -2 , AM (air mass) 1.5, irradiation area 0.08 cm 2 , room temperature (25℃ The measurement can be performed under conditions of about 1000 nm to 1500 nm, and more specifically, by the method described in the Examples. EXAMPLES
[0216] The present invention will be described in more detail below with reference to examples. The methods for preparing the raw materials used are described below.
[0217] [Preparation of raw materials] (FTO substrate (first electrode)) Glass substrate coated with fluorine-doped tin oxide (Glass substrate thickness: 1.8 mm, FTO coating thickness: approximately 900 nm) in acetone After ultrasonic cleaning, the substrate was ultrasonically cleaned in methanol. After drying under nitrogen gas, The specimen was subjected to UV-ozone treatment for 20 minutes.
[0218] (Electron transport layer precursor solution (0.15M)) Titanium diisopropoxide bis(acetylacetonate) bis(acetyl acetonate, Sigma-Aldrich) 0.055 mL and 1-butanol (Nacala It was mixed with 1 mL of Itesque Co., Ltd. (purity 99%) and stirred to prepare the solution.
[0219] (Electron transport layer precursor solution (0.30M)) 0.11 mL of titanium diisopropoxide bis(acetylacetonate) and 1-butanol The mixture was mixed with 1 mL of ethanol and stirred to prepare a solution.
[0220] (Porous part forming solution) 100 mg of TiO2 powder (AEROXIDE TiO2P25 manufactured by Nippon Aerosil Co., Ltd.) and polyethylene 10 mg of ethylene glycol (Nacalai Tesque, Inc. "PEG (♯20000)") 0.5 mL of ultrapure water was added and stirred. Co., Ltd., purity 99%) 10.0 μL, 4-(1,1,3,3-tetramethylbutyl) 5.0 μL of phenyl-polyethylene glycol (Sigma-Aldrich "Triton-X-100") After adding the mixture and stirring for 30 minutes, the mixture was left to stand for a day to prepare the mixture.
[0221] (Perovskite layer precursor solution 1) CH3NH3I (monomethylamine hydroiodide or MAI, Tokyo Chemical Industry Co., Ltd.) (Lead(II) chloride, Sigma-Aldrich Co., Ltd., purity 99.0%) 190.7 mg, , purity 99.999%) 111.2 mg, and N,N-dimethylformamide (DMF The mixture was heated to 60° C. and stirred for one day.
[0222] (Perovskite layer precursor solution 2) CH3NH3I 181.1mg, CH3NH3Br (monomethylamine hydrobromide Or MABr, Showa Chemical Co., Ltd. (purity 98.5%) 6.7 mg, PbCl2111 0.2 mg and 0.5 mL of DMF were mixed, heated to 60°C and stirred for one day.
[0223] (Perovskite layer precursor solution 3) CH3NH3I 181.1mg, HC(NH2)2Br (formamidine hydrobromide Salt or FABr, Tokyo Chemical Industry Co., Ltd. (purity 98%) 7.5 mg, PbCl211 1.2 mg of the compound and 0.5 mL of DMF were mixed, heated to 60° C., and stirred for one day.
[0224] (Perovskite layer precursor solution 4) CH3NH3I 184.3mg, CH3CH2NH3Br (monoethylamine bromide aqueous solution) Peroxidase salt or EABr, Tokyo Chemical Industry Co., Ltd. (purity 98.0%) 5.0 mg, PbCl Mix 2111.2 mg and 0.5 mL of DMF, heat to 60°C and stir for one day. Ta.
[0225] (Perovskite layer precursor solution 5) CH3NH3I 178.0mg, CH3CH2NH3Br 10.1mg, PbCl Mix 2111.2 mg and 0.5 mL of DMF, heat to 60°C and stir for one day. Ta.
[0226] (Perovskite layer precursor solution 6) CH3NH3I 166.7mg, HC(NH2)2I(formamidine hydroiodide Salt or FAI, Tokyo Chemical Industry Co., Ltd., purity 98.0%) 20.6 mg, KI (iodide Potassium, Fujifilm Wako Pure Chemical Industries, Ltd. (purity 99.5%) 3.3 mg, PbCl2 111.2 mg of the product and 0.5 mL of DMF were mixed, heated to 60° C., and stirred for one day.
[0227] (Perovskite layer precursor solution 7) CH3NH3I 156.4mg, HC(NH2)2I 31.0mg, KI3.3m g, 111.2 mg of PbCl2, and 0.5 mL of DMF were mixed and heated to 60 °C. The mixture was stirred for one day.
[0228] (Perovskite layer precursor solution 8) CH3NH3I 98.8mg, PbI2 (lead(II) iodide, Sigma-Aldrich, pure 99.999%) 289.3 mg, γ-butyrolactone (Nacalai Tesque, Inc., pure Mix 0.275 mL of ethyl acetate (98%) and 0.225 mL of DMF and heat to 60°C. The mixture was stirred for one day.
[0229] (Polysilane layer forming solution) Decaphenylcyclopentasilane (OG SOL SI-30-10 (hereinafter simply referred to as DPPS) 10 mg, chlorobenzene (Fujifilm Mix 0.5 mL of 100% dimethylformamide (Wako Pure Chemical Industries, Ltd.) and stir at room temperature (approximately 25°C) for one day to form a polysilane. A solution for forming a crystalline layer was prepared.
[0230] (Hole transport layer forming solution) 2,2',7,7'-Tetrakis-[N,N-di(4-methoxyphenyl)amino]- 9,9'-Spirobifluorene (2,2',7,7'-tetrakis-[N,N-di(4-methoxyphenyl)amino]- 9,9'-spirobifluorene (Sigma-Aldrich, simply called Spiro-OMeTAD) 36.1 mg Add 0.5 mL of chlorobenzene (FUJIFILM Wako Pure Chemical Industries, Ltd.) and stir for 12 hours. Solution A was prepared. Lithium bis(trifluoromethylsulfonyl)imide (Li -TFSI (Tokyo Chemical Industry Co., Ltd.) 260 mg, acetonitrile (Fujifilm Wako The total amount of solution A was added to 0.5 mL of 1,0 ... 8.8 μL of solution B and 14.4 μL of 4-t-butylpyridine (Sigma-Aldrich) The above was mixed and stirred at 70° C. for 30 minutes to prepare a solution for forming a hole transport layer.
[0231] [Fabrication of photoelectric conversion element] Example 1 Using the above materials, a photoelectric conversion element shown in Figure 1 was fabricated. The electron transport layer precursor solution (0.15 M) was dropped and coated with a spin coater (Mikasa Co., Ltd.'s "MS- After spin coating (3000 rpm, 30 seconds) using a 100% ethanol solution, The plate was then heat-treated (125°C, 5 minutes) using a plate ("ND-1" manufactured by AS ONE Corporation). Drop the electron transport layer precursor solution (0.30 M) and spin coat (3000 rpm, 30 seconds). The electron transport layer precursor solution (0.30M) was spin-coated twice, and then hot-coated. The plate was then heat-treated (125°C, 5 minutes). The resulting layer was then heat-treated (550°C, 30 min) at 37°C in a vacuum chamber (200°C-2") to form an electron transport layer (dense Ti O2 layer) was formed.
[0232] The porous portion forming solution was dropped onto the electron transport layer, and spin-coated (5000 rpm, After that, it is heat treated in an electric furnace (550℃, 30 minutes) to a thickness of about 300 to 900 mm. A porous portion (porous TiO2 portion) of about 1 mm was formed.
[0233] A perovskite layer precursor solution heated to 70° C. is placed inside the porous portion (or in the voids). Drop 1 and let it soak in, then spin coat (1000 rpm for 5 seconds, then 2000 rpm for 60 seconds). The perovskite precursor solution was then heated for 10 seconds to form a film containing the perovskite precursor. The operation of dropping and spin coating was performed three times in total. In this case, the crystal nuclei were generated by the air-blowing method. A heating gun (Hakko Corporation's "HEATING GUN 882") was used to heat the substrate. The third spin coat was performed while spraying the liquid toward the starting point. After 45 seconds, the polysilane layer forming solution is dropped to form the perovskite precursor. A thin polysilane layer was laminated on the film containing 19 The perovskite crystals are grown by heat treatment at 0°C for 10 minutes to a thickness of approximately 300 to 900 nm. The first perovskite layer (the voids in the porous part are impregnated or infiltrated with perovskite compounds) is A layer containing a perovskite compound) and a second perovskite layer with a thickness of about 100 nm. As described later, this heat treatment By this, an electron blocking layer (PbI2 The formation of a layer was also confirmed.
[0234] A hole transport layer forming solution was dropped onto the polysilane layer and spin-coated (4000 rp m for 30 seconds to form a hole transport layer having a thickness of about 40 nm.
[0235] The above-mentioned film formation from the electron transport layer to the hole transport layer was all carried out in the air.
[0236] Thereafter, a vacuum deposition apparatus (SVC-70 manufactured by Sanyu Electronics Co., Ltd.) was used to deposit a thin film of 10 ... Gold (Au) is evaporated (or deposited) using a 0TMSG / 7PS800E to a thickness of approximately 20 In this way, the photoelectric conversion element shown in FIG. Made.
[0237] Example 2 The heat treatment conditions for growing perovskite crystals were changed to 210°C for 10 minutes. A photoelectric conversion element was produced in the same manner as in Example 1.
[0238] Example 3 Instead of the perovskite layer precursor solution 1, the perovskite layer precursor solution 2 was used. The heat treatment conditions for growing perovskite crystals were changed to 190°C and 10 minutes. A photoelectric conversion element was produced in the same manner as in Example 1.
[0239] Example 4 Instead of the perovskite layer precursor solution 1, the perovskite layer precursor solution 3 was used. The heat treatment conditions for growing perovskite crystals were changed to 190°C for 3 minutes. A photoelectric conversion element was produced in the same manner as in Example 1.
[0240] Example 5 Instead of the perovskite layer precursor solution 1, the perovskite layer precursor solution 4 was used. The heat treatment conditions for growing perovskite crystals were changed to 200°C and 10 minutes. A photoelectric conversion element was produced in the same manner as in Example 1.
[0241] Example 6 Instead of the perovskite layer precursor solution 1, the perovskite layer precursor solution 5 was used. The heat treatment conditions for growing perovskite crystals were changed to 200°C and 10 minutes. A photoelectric conversion element was produced in the same manner as in Example 1.
[0242] Example 7 Instead of the perovskite layer precursor solution 1, the perovskite layer precursor solution 6 was used. The heat treatment conditions for growing perovskite crystals were changed to 180°C and 10 minutes. A photoelectric conversion element was produced in the same manner as in Example 1.
[0243] Example 8 The heat treatment conditions for growing perovskite crystals were changed to 200°C and 10 minutes. A photoelectric conversion element was produced in the same manner as in Example 7.
[0244] Example 9 Instead of the perovskite layer precursor solution 1, the perovskite layer precursor solution 7 was used. The heat treatment conditions for growing perovskite crystals were changed to 180°C and 10 minutes. A photoelectric conversion element was produced in the same manner as in Example 1.
[0245] Comparative Example 1 The conditions of the heat treatment for growing perovskite crystals without forming a polysilane layer are as follows: A photoelectric conversion element was prepared in the same manner as in Example 1, except that the temperature was changed to 140° C. for 10 minutes. did.
[0246] Comparative Example 2 Instead of the perovskite layer precursor solution 1, the perovskite layer precursor solution 8 was used, and The heat treatment conditions for growing perovskite crystals without forming a silane layer were set as follows: A photoelectric conversion element was prepared in the same manner as in Example 1, except that the temperature was changed to 0° C. for 10 minutes. .
[0247] Comparative Example 3 A photoelectric conversion element was fabricated in the same manner as in Example 2 of JP 2018-98276 A (Patent Document 4). A child was created.
[0248] Comparative Example 4 A photoelectric conversion element was fabricated in the same manner as in Example 3 of JP 2019-68018 A (Patent Document 5). A child was created.
[0249] Comparative Example 5 A photoelectric conversion element was prepared in the same manner as in Comparative Example 4 of JP 2018-98276 A (Patent Document 4). A child was created.
[0250] In addition, in the perovskite layer precursor solution of Comparative Example 4 of Patent Document 4, When the heat treatment conditions for growing the perovskite crystals are changed to a high temperature of about 180 to 200 °C, the perovskite crystals grow. Since it is expected that the kite crystals will decompose, the fabrication of photoelectric conversion elements by high-temperature heat treatment is prohibited. I was careful.
[0251] [XRD (X-ray diffraction) measurement] Using an X-ray diffraction device (Bruker AXS "D2 PHASER"), XRD (X-ray diffraction) was measured for the photoelectric conversion element. 7 and Comparative Example 4 are shown as representative examples of X-ray diffraction patterns immediately after device fabrication.
[0252] As is clear from FIG. 2, a peak of PbI2 is confirmed in the diffraction pattern of Example 7. This indicates that a PbI2 layer (electron blocking layer) exists between the perovskite layer and the polysilane layer. It is considered that the diffraction patterns of not only Example 7 but also all Examples show that The PbI2 peak was also confirmed.
[0253] In addition, the diffraction pattern of Example 7 produced by the air blow method and high-temperature heat treatment was It was confirmed that the orientation of the (100) plane of the perovskite crystal was very high compared to Comparative Example 4. It was.
[0254] Furthermore, based on the results of XRD measurement in Example 1 and Comparative Examples 3 and 4, perovskite The lattice constant a of the crystal was calculated by the least squares method, and the results are shown in Table 1.
[0255] [Table 1]
[0256] As is clear from Table 1, in Example 1, the perovskite crystals of the same composition were used in Comparative Examples 3 and 4. In contrast, the lattice constant a was slightly enlarged because the desorption of MA was effectively suppressed.
[0257] [Evaluation of photoelectric conversion element characteristics] Precision source / measure unit (KEYSIGHT "B2901A"), Light source: Xenon laser simulator (Minakata Electric Manufacturing Co., Ltd. "XES-301S") lamp, illuminance: 100mWcm -2 ) with AM (air mass) 1.5 and irradiation area 0.08 cm 2 Under room temperature (about 25° C.), the photoelectric conversion elements obtained in the examples and comparative examples The current density-voltage curve was measured. Note that light was irradiated through the FTO substrate side of the photoelectric conversion element. The measurement results are shown in Table 2 and Figure 3.
[0258] In Table 2, in the column for the perovskite layer, MA stands for methylammonium (C H3NH3), EA is ethylammonium (CH3CH2NH3), and FA is formamide. nium (HC(NH2)2), and Jsc-0 , V oc-0 and η0 is the device The initial short-circuit current density, open-circuit voltage, and photoelectric conversion efficiency after fabrication of the device are shown in Fig. 1. sc -x , V oc-x and η x is the short circuit current after x weeks (xW) in air after device fabrication The density, open circuit voltage and photoelectric conversion efficiency are shown in Fig. 1. Also, η0 and η x Reverse (Reverse scan, scanning in the direction of decreasing voltage) indicates the maximum value.
[0259] [Table 2]
[0260] As is clear from Table 2 and FIG. 3, in all of the Examples, the results were higher than those of the Comparative Example in the atmosphere. Despite being heat-treated at high temperatures, the cells showed high conversion efficiency and durability. In Examples 5 to 6 including FA and K, and in Examples 7 to 9 including FA and K, particularly in Example 7, High conversion efficiency was observed even after a long period of time. The short circuit current density was high, and in Examples 7 to 9 containing FA and K, the open circuit voltage tended to be high. It was confirmed.
[0261] In Example 7, where η0 is low, there are regions that are not completely crystalline, and the perovskite structure It is believed that the conversion efficiency was improved by room temperature aging of the kite crystal. The initial crystallite size D of the (100) plane after device fabrication was approximately 130 nm. After 26 weeks (after 26W), the diameter was about 270 nm, indicating that the crystals had grown. In addition, the conversion efficiency η5 after 5 weeks (after 5 W) of Example 7 exceeded about 6%, The crystallite size D was calculated based on the results of XRD measurement using the Scherrer formula ( Scherrer's equation) [D=0.9×λ / (β×cosθ), where D is the crystallite size , λ is the wavelength of the X-ray (0.15405 nm), β is the full width at half maximum (FWHM) corrected for the instrument constant M), θ is the Bragg angle.
[0262] On the other hand, in Example 8, in which the heat treatment temperature was changed to 200° C. compared to Example 7, η0 was The efficiency was high and stable over a long period of time from the initial stage.
[0263] Similar characteristic evaluations were also performed for Comparative Examples 3 to 5, but the conversion efficiency in all cases decreased within about one week. The durability evaluation test was discontinued because the η had dropped significantly to approximately 90-60% of η0. [Industrial Applicability]
[0264] The present invention relates to a perovskite-type photoelectric conversion element (perovskite-type photoelectric conversion element) having high conversion efficiency. It can be effectively used as a compound photoelectric conversion thin film device or a perovskite type solar cell. In addition, the photoelectric conversion element of the present invention has the following advantages compared to the Si-based solar cells that are currently widely used: Because it uses a direct transition semiconductor, it has a high external quantum efficiency in the visible light wavelength range and is suitable for indoor use. This material has the potential to be used in IoT devices that require small, lightweight, and flexible properties. do. [Explanation of symbols]
[0265] 1...First electrode 2...Electron transport layer (ETL) 3a…First perovskite layer 3b…Second perovskite layer 4...Electron blocking layer 5...Polysilane layer 6...Hole transport layer (HTL) 7...Second electrode
Claims
1. A photoelectric conversion element including an electron transport layer, a perovskite layer including a compound having a perovskite structure, an electron blocking layer including a p-type semiconductor, a polysilane layer including a polysilane, and a hole transport layer, the perovskite layer, the electron blocking layer, the polysilane layer, and the hole transport layer are sequentially stacked on one surface of the electron transport layer; The polysilane is represented by the following formulas (2a) and (2b): 【Chemistry 1】 (In the formula, R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, an organic group, or a silyl group. At least one structural unit selected from the structural units represented by A photoelectric conversion element in which the proportion of the polysilane is 70 to 100% by mass based on the entire polysilane layer.
2. In the formula (2a), R 1 and R 2 At least one of the groups is an aryl group-containing group, and in the formula (2b), R 3 2. The photoelectric conversion element according to claim 1, wherein is an aryl group-containing group.
3. 3. The photoelectric conversion element according to claim 1, wherein the ratio of the structural unit represented by the formula (2a) is 50 mol % or more based on the entire polysilane.
4. 4. The photoelectric conversion element according to claim 1, wherein the polysilane is a cyclic polysilane.
5. The compound having a perovskite structure is represented by the following formula (1): AMX 3 (1) (In the formula, A represents a monovalent cation including at least one selected from organic ammonium, amidinium, and alkali metal ions, M represents a divalent cation of at least one metal element selected from elements in Group 14 of the periodic table and elements in Group 2 of the periodic table, and X represents a halide ion.) The photoelectric conversion element according to any one of claims 1 to 4, wherein the compound is represented by the formula:
6. A in the formula (1) is methylammonium and C 2-4 Alkyl ammonium, C 1-4 6. The photoelectric conversion element according to claim 5, further comprising at least one second monovalent cation selected from the group consisting of amidinium, sodium ion, potassium ion, rubidium ion and cesium ion.
7. 7. The photoelectric conversion element according to claim 6, wherein the ratio of the methylammonium to the total amount of the second monovalent cations is the former / latter (molar ratio)=40 / 60 to 98 / 2.
8. The photoelectric conversion element according to any one of claims 5 to 7, wherein the compound having a perovskite structure contains, as X in the formula (1), an iodide ion and at least one second halide ion selected from a bromide ion and a chloride ion.
9. 9. The photoelectric conversion element according to claim 8, wherein the ratio of the total amount of the iodide ions to the total amount of the second halide ions (the former / the latter (molar ratio)) is 80 / 20 to 98 / 2.
10. The p-type semiconductor is represented by the following formula (1b): MX 2 (1b) (In the formula, M represents a divalent cation of at least one metal element selected from the group consisting of elements in Group 14 of the periodic table and elements in Group 2 of the periodic table, and X represents a halide ion.) The photoelectric conversion element according to any one of claims 1 to 9, wherein the compound is represented by the formula:
11. The method for producing a photoelectric conversion element according to any one of claims 1 to 10, comprising: a perovskite precursor film forming step of forming a film containing a perovskite precursor for forming a compound having a perovskite structure on one surface of an electron transport layer; a polysilane layer forming step of laminating a polysilane layer containing polysilane on the film containing the perovskite precursor to form a preliminary laminate; a heat treatment step of heat treating the preliminary laminate obtained in the polysilane layer forming step at 160 to 250°C to form a laminate containing a perovskite layer, an electron blocking layer, and a polysilane layer; and a hole transport layer forming step of laminating a hole transport layer on the surface of the polysilane layer of the laminate formed in the heat treatment step.
12. The method according to claim 11, wherein the polysilane layer forming step and the heat treatment step are carried out in air.
13. The method according to claim 11 or 12, further comprising a porous portion forming step of forming a porous portion on one surface of the electron transport layer as a pre-step of a perovskite precursor film forming step.
Citation Information
Patent Citations
Hybrid solar cell
JP2015119102A
Fullerene compound, semiconductor device, solar cell and solar cell module
JP2016210750A
Photoelectric conversion element and manufacturing method thereof
JP2018098276A
Solar cell and method for manufacturing the same
JP2019145621A
Method for manufacturing semiconductor device
JP2019220701A